Isolating Effects of Temperature and Light on Nutrient Acquisition by Biofilm and Bryophyte Communities in Arctic Spring-Stream Ecosystems - Tori A. Hebert; Adam C. Hensley; Carla L. Atkinson; Jonathan P. Benstead; Alexander D. Huryn (Ecosystems, 2026)

Phylogenomic analyses reveal introgression and cryptic speciation in the globally distributed, vector-transmitted pathogen Plasmodium relictum - Esther Weyer; Angela N. Theodosopoulos; Vaidas Palinauskas; Staffan Bensch; Helena Westerdahl; Mélanie Duc; Arif Ciloglu; Xi Huang; Kyeong Soon Kim; Yoshio Tsuda; Carter T. Atkinson; Pavel Zehtindjiev; et al. (Molecular Phylogenetics and Evolution, 2026)

Environmental influences on terminal migration behaviour of Chinook salmon in Cowichan Bay, British Columbia - Kelsie A. Murchy; William D.P. Duguid; Jamieson B. Atkinson; Jessica Qualley; Katie G. Innes; Hailey L. Davies; Bridget Maher; Francis Juanes (Fisheries Research, 2026)

Comparative Effects of Thermal Recovery Strategies on Strength, Muscle Soreness and Molecular Markers Following Exercise-Induced Muscle Damage in Healthy Adults - F. Bayne; M. Nagyova; N. Stolk; M.A. Placido; M. Hamdi; A. Falzon; R. Perezen; S. Neto Menezes; S. Haliti; C. Atkinson; S. Racinais; N. Gaoua (Journal of Thermal Biology, 2026)

Extreme site fidelity in long‐distance migratory shorebirds in Australia and potential implications for conservation - Tobias A. Ross; Robyn Atkinson; Maureen Christie; Danny I. Rogers; Chris Hassell; Roz Jessop; Jonathan T. Coleman; Theunis Piersma; Sara Ryding; Aaron Spence; Marcel Klaassen (Conservation Biology, 2026)
Site fidelity is the tendency for animals to repeatedly return to the same locations, either within or between years. Site fidelity enables animals to utilize knowledge of previously visited locations, including assessments of seasonal variations in health and mortality risks (e.g., predation), resource availability, and social benefits such as pairing with previous mates. However, rigidly enacted site fidelity may come with fitness costs in times of rapid habitat change. One group believed to exhibit site fidelity is migratory shorebirds (families Charadriidae and Scolopacidae). Shorebirds that migrate annually via the East Asian–Australasian Flyway have experienced rapid population declines due to habitat loss in Asia. Although high site fidelity may influence these declines under a global change scenario, only limited, species‐specific analyses of site fidelity have been previously conducted. Our study used an extensive dataset of 636,167 records of over 84,000 banded individual shorebirds from 1976 to 2025 to present an overview of site fidelity for 12 migratory shorebird species during their nonbreeding season in Australia. We found overall site fidelity of >95% across 10 out of 12 species, with the only exceptions being red knot ( Calidris canutus ) and sanderling ( Calidris alba ), with movements often limited to sections of coastline less than 20 km long. Juvenile and immature birds were usually less site faithful than adults. The high site fidelities of most species suggest that local site knowledge is of considerable importance and that individuals forced to relocate to alternative sites will likely incur a cost. Our findings also imply that habitat loss may have immediate population‐level consequences through reduced fitness of displaced birds.

Muscle Ageing and Sarcopenia Study (MASS) Lifecourse: a valuable resource for understanding skeletal muscle ageing - Rachel Cooper; Christopher Hurst; Holly Syddall; Helen Atkinson; Jonathan G. Bunn; Daniela Carpinelli; Antoneta Granic; Susan J. Hillman; Emma Grace Lewis; Claire McDonald; Katie Sloan; Karen Suetterlin; et al. (GeroScience, 2026)

Sex-associated variables – A framework for neurotoxicology - Cameron P. Hamson; Morgan L. Atkinson; Troy A. Roepke (NeuroToxicology, 2026)

Revisiting Europe's temperate forests: Palaeoecological evidence for an herbivory-driven woodland-grassland mosaic biome - Szymon Czyżewski; Skjold Alsted Søndergaard; Ábel Péter Molnár; Matthew Roy Kerr; Jeppe Aagaard Kristensen; Joe Atkinson; Jonas Trepel; Maciej Sykut; Paweł Radzikowski; Signe Sangill Termansen; Karol Wałach; Elena A. Pearce; et al. (Biological Conservation, 2026)

Relative accuracy of point-of-care tests to rule-in heartworm infection in clinically suspected dogs using Bayesian latent class modelling - P.J. Atkinson; C. Quimby; A. Datt; T.D. Nielsen; C.G.B. Caraguel (Preventive Veterinary Medicine, 2026)

Paraglacial conditions, climate and isostacy control river incision and terrace development; the example of the River Lune, NW England - Paul A. Carling; Mahmoud Abbas; Xianjiao Ou; Jialing Cai; Ying Ying Ding; Peter.M. Atkinson; Xujiao Zhang; Yanlian Zhou (Geomorphology, 2026)

Diarrhoea in children under 5 years in two informal settlements in Accra, Ghana: The impact of antecedent rainfall and flooding - Mehmet A. Veral; Manoj Roy; Roger W. Pickup; Richard Bayitse; Pat M. Agbedor; Mark Akrong; Peter M. Atkinson (Environmental Research, 2026)

Hatchery-reared coho salmon develop less otolith deformities in tanks with alternating water flow directions - Leigh P. Gaffney; Emma B. Polard; Lydia N. Walton; Chloe Kraemer; Zoe A. Molder; Garth A. Covernton; Jamieson Atkinson; Laura Elmer; Samantha James; Thomas Negrin; Micah Quindazzi; Will Duguid; et al. (Aquaculture, 2026)

Identification of Nuclearity of Chromium Binary Adducts with DNA by Negative Ion Mass Spectrometry: Short Communication - Kaleb Kovitch; Qiaoli Liang; Katie Repke; Elizabeth K. Atkinson; Stephen A. Woski; John B. Vincent (Biological Trace Element Research, 2025)

Genetics services in Latin America: a descriptive study of availability and utilization of genetics in healthcare - Ryan J. German; Erin Atkinson; Eric A. Storch; Claudia Soler-Alfonso; Sonia Margarit; Philip J. Lupo; Stacey Pereira (Journal of Community Genetics, 2025)

A role for dendroecology in guiding hydrologic restoration and mitigating risks of peatland soil loss: an example from Chamaecyparis thyoides forests - Robert B. Atkinson; Abigail Weaver; Joshua A. Kincaid; Frederic C. Wurster; James M. B. Doyle (Trees, 2025)
Key message Tree rings of Chamaecyparis thyoides exhibit growth responses that are influenced by local hydrologic conditions through decadal timescales. That perspective can assist peatland natural resource managers in selection of hydrologic restoration targets that minimize chronic microbial oxidation and acute peat loss associated with fire. Abstract Temperate forested peatlands are valued for myriad ecosystem services including carbon storage and biodiversity which may be lost through anthropogenic disturbance of hydrologic regimes. Hydrologic alterations may be recorded in tree stem growth patterns and provide insights for management and restoration. In Chamaecyparis thyoides (Atlantic White Cedar, Juniper) swamps, stand drainage causes a shift from net soil carbon sink to source as microbial oxidation and catastrophic fire oxidize stored organic matter. Here, we analyze historic radial growth patterns in C. thyoides in order to characterize drainage history to guide hydrologic management for peat conservation and restoration. Basal area increment (BAI) estimates across a ~ 60-year chronology (1939–2003) were analyzed by flexible beta cluster analysis of 185 trees from 13 C. thyoides stands in the Great Dismal Swamp National Wildlife Refuge in Virginia and North Carolina, USA. Stands formed 3 groups, and growth rates among all groups were indicative of a drained hydrologic regime throughout the chronology compared to an undrained control stand. Regime shift analyses identified positive shifts for 2 stand groups in 1954 and for all 3 stand groups in 1963. Multiple response permutation procedures and partial mantel tests both identified two predictive growth variables including (1) visual observations of fluctuation in the water table and (2) proximity to a primary ditch. Growth rate was suppressed when weirs were installed in the mid-1980s; however, growth rebounded within ~ 2 years. The chronology ends when stands were struck by a major hurricane in 2003 and fires in 2008 and 2011 liberated 1.38 Tg of peat carbon. We conclude that dendroecology can detect hydrologic changes through time and can reduce risks of microbial oxidation and catastrophic fire in forested peatlands.

Pace of alcohol drinking during in natural-environment drinking is associated with heightened alcohol-related reward and negative consequences in risky drinkers - Emily A. Atkinson; Andrew M. Fischer; John F. Cursio; Andrea C. King; Daniel J. Fridberg (Psychopharmacology, 2025)

Seasonally migrating zooplankton strongly enhance Southern Ocean carbon sequestration - Guang Yang; Angus Atkinson; Evgeny A. Pakhomov; Katrin Schmidt; Weilei Wang; Jennifer J. Freer; Geraint A. Tarling (Limnology and Oceanography, 2025)
High‐latitude zooplankton can sequester millions of tons of carbon due to their seasonal migration from the surface ocean to depth, and their respiration and mortality during overwintering. This seasonal vertical migration pump (SVMP) efficiently removes carbon but not limiting nutrients such as iron from the surface layers. However, this process is not included in Earth System Models and whole Southern Ocean estimates are still lacking. Here, we compile large datasets of Southern Ocean zooplankton biomass and physiology to estimate that the SVMP transports 65 Mt carbon annually to sequestration‐achieving depths of > 500 m. Mesozooplankton are the main agents (80%), followed by krill (14%), and salps (6%), with respiration and mortality at depth contributing a similar share. This SVMP adds greatly to existing modeled or measured estimates of Southern Ocean carbon sequestration, equating to 38–56% of particulate organic carbon flux at 500 m and 78–103% of the flux at 1000 m. Given their large biomass but projected change under polar warming, understanding how zooplankton transport carbon and nutrients will underpin improved model projections of ocean carbon storage in a warmer world.

European Breeding Bird Declines Associated With Narrower Climatic Niches - Karolina Zalewska; James J. Gilroy; Inês Catry; Philip W. Atkinson; Alena Klvaňová; Aldina M. A. Franco (Journal of Biogeography, 2025)
Aim Anthropogenic climate change has increasingly been identified as a major threat to global biodiversity. However, the extent of this threat is likely to be uneven across species, due to differences in life histories or exposure to environmental change. The range of climatic conditions a species experiences across its range extent, known as the realised climatic niche, may be an indicator of species resilience to climate change. Species with large range extents, occurring across diverse climatic conditions, are expected to be less affected by climate change due to lower physiological constraints and tolerance to a wider range of climates. However, this may not be the case if local populations are adapted to specific environmental conditions. In this study, we investigate whether the extent of the species' realised climatic niche, also known as the climatic niche breadth, is linked to their long‐term population trends. Location Europe. Taxon Birds. Methods We extract climate data across the breeding‐only and resident ranges of 159 European bird species and use an ordination method to produce a representation of the species climatic niches. We then relate the niche breadth of each species to their range area and incorporate this relationship, along with the species' diet, main habitat type, migratory status and average body mass, to investigate their relationship with the species long‐term population trend. Results Species with small range areas showed larger variation in climatic niche breadth than species with larger ranges. For species with similar range areas, those with broader climatic tolerance were less likely to be declining than those with narrow climatic niches. Main Conclusions These findings can help us understand the threats associated with climate change and allow for rapid assessment of the importance of climatic factors on population trends, providing an invaluable tool for targeting habitat conservation.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Correction to: Biomarkers of cellular senescence and major health outcomes in older adults - Steven R. Cummings; Li‑Yung Lui; Zaira Aversa; Theresa Mau; Roger A. Fielding; Elizabeth J. Atkinson; Sheena Patel; Nathan LeBrasseur (GeroScience, 2025)

A Paleocene occurrence of cornelian cherries Cornus subg. Cornus in the land-mammal site of Berru (Paris Basin, France) - Cédric Del Rio; Brian A. Atkinson; Thierry Smith (Review of Palaeobotany and Palynology, 2025)

Biomarkers of cellular senescence and major health outcomes in older adults - Steven R. Cummings; Li-Yung Lui; Aversa Zaira; Theresa Mau; Roger A. Fielding; Elizabeth J. Atkinson; Sheena Patel; Nathan LeBrasseur (GeroScience, 2024)
The geroscience hypothesis proposes that underlying biological processes, such as the accumulation of senescent cells, have deleterious effects on multiple tissues and increase the risk of many chronic conditions with aging. Senescent cells produce heterogenous biomarkers, also called senescence-associated secretory phenotype (SASP). Circulating concentrations of senescence biomarkers may reflect an underlying burden of senescent cells in various tissues. Plasma levels of these proteins have been associated with increased mortality and poorer physical function. The associations of them with the incidence of major age-related conditions including heart failure, cardiovascular disease, stroke, and dementia, have not been studied. We measured 35 senescence biomarkers in baseline plasma samples from 1678 participants aged 70–79 years old in the longitudinal Health ABC cohort study. Clinical outcomes were ascertained and validated over an average 11.5 year follow-up. In models adjusted for age, sex, and race, higher levels of most of senescence biomarkers were associated with increased risk of all-cause mortality, mobility limitation, and heart failure. Several were also associated with an increased risk of coronary heart disease, stroke, and dementia. Very few were associated with the risk of cancer. Proteins that were selected by Lasso regression for each outcome that commonly included GDF15 and IL6, significantly improved the prediction of mortality, mobility limitation, and heart failure compared with age, sex, and race alone. These results indicate that levels of senescence biomarkers predict an increased risk of several age-related clinical outcomes and may identify individuals most likely to benefit from senotherapeutics.

Per- and poly-fluoroalkyl substances (PFAS) do not accumulate with age or affect population survival in ruddy turnstone (Arenaria interpres) - Tobias A. Ross; Junjie Zhang; Tonje G. Skaalvik; Robyn Atkinson; Roz Jessop; Alexandros G. Asimakopoulos; Veerle L.B. Jaspers; Marcel Klaassen (Science of The Total Environment, 2024)

Shorebirds Are Shrinking and Shape‐Shifting: Declining Body Size and Lengthening Bills in the Past Half‐Century - A. McQueen; M. Klaassen; G. J. Tattersall; S. Ryding; R. Atkinson; R. Jessop; C. J. Hassell; M. Christie; A. Fröhlich; M. R. E. Symonds (Ecology Letters, 2024)
Animals are predicted to shrink and shape‐shift as the climate warms, declining in size, while their appendages lengthen. Determining which types of species are undergoing these morphological changes, and why, is critical to understanding species responses to global change, including potential adaptation to climate warming. We examine body size and bill length changes in 25 shorebird species using extensive field data (> 200,000 observations) collected over 46 years (1975–2021) by community scientists. We show widespread body size declines over time, and after short‐term exposure to warmer summers. Meanwhile, shorebird bills are lengthening over time but shorten after hot summers. Shrinking and shape‐shifting patterns are consistent across ecologically diverse shorebirds from tropical and temperate Australia, are more pronounced in smaller species and vary according to migration behaviour. These widespread morphological changes could be explained by multiple drivers, including adaptive and maladaptive responses to nutritional stress, or by thermal adaptation to climate warming.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Labrador Coastal Current and productivity variations offshore Nain (Nunatsiavut) during the late Holocene - M. Atkinson; A. Normandeau; N. Van Nieuwenhove; A. de Vernal; M. Saunders; J. Woollett; A. Limoges (Quaternary Science Reviews, 2024)

Construction and validation of an infant chest phantom for paediatric computed tomography - Seonaid Rodgers; Janette Atkinson; David Cryer; Cameron Storm; Rikki Nezich; Martin A. Ebert; Pejman Rowshanfarzad (Physical and Engineering Sciences in Medicine, 2024)
Paediatric imaging protocols should be carefully optimised to maintain the desired image quality while minimising the delivered patient dose. A paediatric chest phantom was designed, constructed and evaluated to optimise chest CT examinations for infants. The phantom was designed to enable dosimetry and image quality measurements within the anthropomorphic structure. It was constructed using tissue equivalent materials to mimic thoracic structures of infants, aged 0–6 months. The phantom materials were validated across a range of diagnostic tube voltages with resulting CT numbers found equivalent to paediatric tissues observed via a survey of clinical paediatric chest studies. The phantom has been successfully used to measure radiation dose and evaluate various image quality parameters for paediatric specific protocols.

Observing change in pelagic animals as sampling methods shift: the case of Antarctic krill - Simeon L. Hill; Angus Atkinson; Javier A. Arata; Anna Belcher; Susan Bengtson Nash; Kim S. Bernard; Alison Cleary; John A. Conroy; Ryan Driscoll; Sophie Fielding; Hauke Flores; Jaume Forcada; et al. (Frontiers in Marine Science, 2024)
Understanding and managing the response of marine ecosystems to human pressures including climate change requires reliable large-scale and multi-decadal information on the state of key populations. These populations include the pelagic animals that support ecosystem services including carbon export and fisheries. The use of research vessels to collect information using scientific nets and acoustics is being replaced with technologies such as autonomous moorings, gliders, and meta-genetics. Paradoxically, these newer methods sample pelagic populations at ever-smaller spatial scales, and ecological change might go undetected in the time needed to build up large-scale, long time series. These global-scale issues are epitomised by Antarctic krill ( Euphausia superba ), which is concentrated in rapidly warming areas, exports substantial quantities of carbon and supports an expanding fishery, but opinion is divided on how resilient their stocks are to climatic change. Based on a workshop of 137 krill experts we identify the challenges of observing climate change impacts with shifting sampling methods and suggest three tractable solutions. These are to: improve overlap and calibration of new with traditional methods; improve communication to harmonise, link and scale up the capacity of new but localised sampling programs; and expand opportunities from other research platforms and data sources, including the fishing industry. Contrasting evidence for both change and stability in krill stocks illustrates how the risks of false negative and false positive diagnoses of change are related to the temporal and spatial scale of sampling. Given the uncertainty about how krill are responding to rapid warming we recommend a shift towards a fishery management approach that prioritises monitoring of stock status and can adapt to variability and change.

The effects of soil compaction on wheat seedling root growth are specific to soil texture and soil moisture status - Cailian Yu; Tinashe Mawodza; Brian S. Atkinson; Jonathan A. Atkinson; Craig J. Sturrock; Richard Whalley; Malcolm J. Hawkesford; Hannah Cooper; Xiaoxian Zhang; Hu Zhou; Sacha J. Mooney (Rhizosphere, 2024)

Unconfined fishway design, implementation, and assessment for the emerald Shiner (Notropis atherinoides) in the Upper Niagara River, New York - Jundong Qiao; Sean J. Bennett; Joseph F. Atkinson; Paul A. Cocca; Sarah K. Delavan; Andrew R. Hannes; Bryan A. Hinterberger; Timothy J. Pede; Alicia Pérez-Fuentetaja; Richard J. Ruby (Ecological Engineering, 2024)

Essential omega‐3 fatty acids are depleted in sea ice and pelagic algae of the Central Arctic Ocean - Katrin Schmidt; Martin Graeve; Clara J. M. Hoppe; Sinhué Torres‐Valdes; Nahid Welteke; Laura M. Whitmore; Philipp Anhaus; Angus Atkinson; Simon T. Belt; Tina Brenneis; Robert G. Campbell; Giulia Castellani; et al. (Global Change Biology, 2024)
Microalgae are the main source of the omega‐3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), essential for the healthy development of most marine and terrestrial fauna including humans. Inverse correlations of algal EPA and DHA proportions (% of total fatty acids) with temperature have led to suggestions of a warming‐induced decline in the global production of these biomolecules and an enhanced importance of high latitude organisms for their provision. The cold Arctic Ocean is a potential hotspot of EPA and DHA production, but consequences of global warming are unknown. Here, we combine a full‐seasonal EPA and DHA dataset from the Central Arctic Ocean (CAO), with results from 13 previous field studies and 32 cultured algal strains to examine five potential climate change effects; ice algae loss, community shifts, increase in light, nutrients, and temperature. The algal EPA and DHA proportions were lower in the ice‐covered CAO than in warmer peripheral shelf seas, which indicates that the paradigm of an inverse correlation of EPA and DHA proportions with temperature may not hold in the Arctic. We found no systematic differences in the summed EPA and DHA proportions of sea ice versus pelagic algae, and in diatoms versus non‐diatoms. Overall, the algal EPA and DHA proportions varied up to four‐fold seasonally and 10‐fold regionally, pointing to strong light and nutrient limitations in the CAO. Where these limitations ease in a warming Arctic, EPA and DHA proportions are likely to increase alongside increasing primary production, with nutritional benefits for a non‐ice‐associated food web.

Assessment of contaminants, health and survival of migratory shorebirds in natural versus artificial wetlands – The potential of wastewater treatment plants as alternative habitats - Tobias A. Ross; Junjie Zhang; Michelle Wille; Tomasz Maciej Ciesielski; Alexandros G. Asimakopoulos; Prescillia Lemesle; Tonje G. Skaalvik; Robyn Atkinson; Roz Jessop; Veerle L.B. Jaspers; Marcel Klaassen (Science of The Total Environment, 2023)

Combining remote sensing and tracking data to quantify species' cumulative exposure to anthropogenic change - Claire Buchan; James J. Gilroy; Inês Catry; Chris M. Hewson; Philip W. Atkinson; Aldina M. A. Franco (Global Change Biology, 2023)
Identifying when and where organisms are exposed to anthropogenic change is crucial for diagnosing the drivers of biodiversity declines and implementing effective conservation measures. Accurately measuring individual‐scale exposure to anthropogenic impacts across the annual cycle as they move across continents requires an approach that is both spatially and temporally explicit—now achievable through recent parallel advances in remote‐sensing and individual tracking technologies. We combined 10 years of tracking data for a long‐distance migrant, (common cuckoo, Cuculus canorus ), with multi‐dimensional remote‐sensed spatial datasets encompassing thirteen relevant anthropogenic impacts (including infrastructure, hunting, habitat change, and climate change), to quantify mean hourly and total accumulated exposure of tracked individuals to anthropogenic change across each stage of the annual cycle. Although mean hourly exposure to anthropogenic change was greatest in the breeding stage, accumulated exposure to changes associated with direct mortality risks (e.g., built infrastructure) and with climate were greatest during the wintering stage, which comprised 63% of the annual cycle on average for tracked individuals. Exposure to anthropogenic change varied considerably within and between migratory flyways, but there were no clear between‐flyway differences in overall exposure during migration stages. However, more easterly autumn migratory routes were significantly associated with lower subsequent exposure to anthropogenic impacts in the winter stage. Cumulative change exposure was not significantly associated with recent local‐scale population trends in the breeding range, possibly because cuckoos from shared breeding areas may follow divergent migration routes and therefore encounter very different risk landscapes. Our study highlights the potential for the integration of tracking data and high‐resolution remote sensing to generate valuable and detailed new insights into the impacts of environmental change on wild species.

Major declines in NE Atlantic plankton contrast with more stable populations in the rapidly warming North Sea - Matthew M. Holland; Arnaud Louchart; Luis Felipe Artigas; Clare Ostle; Angus Atkinson; Isabelle Rombouts; Carolyn A. Graves; Michelle Devlin; Birgit Heyden; Margarita Machairopoulou; Eileen Bresnan; Jos Schilder; et al. (Science of The Total Environment, 2023)

Relative sea‐level changes in southeastern Australia during the 19 th and 20 th centuries - S. L. Williams; E. Garrett; P. T. Moss; S. Dangendorf; F. D. Hibbert; N. R. Atkinson; V. Pashley; I. L. Millar; M. H. Garnett; A. Zawadzki; W. R. Gehrels (Journal of Quaternary Science, 2023)
Rates of global and regional sea‐level rise between ~1850 and 1950 were high compared to those in preceding centuries. The cause of this sea‐level acceleration remains uncertain, but it appears to be pronounced in a small set of relative sea‐level proxy records from the Southern Hemisphere. Here we generate three new proxy‐based relative sea‐level reconstructions for southeastern Australia to investigate spatial patterns and causes of historical sea‐level changes in the Tasman Sea. Palaeo sea‐level estimates were determined using salt‐marsh foraminifera as sea‐level indicators. Records are underpinned by chronologies based on accelerator mass spectrometry 14 C, radiogenic lead ( 210 Pb), stable lead isotopes and palynological analyses. Our reconstructions show that relative sea level rose by ~0.2–0.3 m over the last 200 years in southeastern Australia, and rates of sea‐level rise were especially high over the first half of the 20 th century. Based on modelled estimates of the contributing components to sea‐level rise, we suggest that the episode of rapid sea‐level rise was driven by barystatic contributions, but sterodynamic contributions were dominant by the mid‐20 th century. Significant spatial variability in relative sea level indicates that local to sub‐regional drivers of sea level are also prominent. Our reconstructions significantly enhance our understanding of the spatiotemporal pattern of early 20 th century sea‐level rise in the region.

Soil structure has a greater effect on the rooting of wheat (Triticum aestivum L.) than nitrogen fertilisation rate or genotype - Tinashe Mawodza; Hu Zhou; Brian S. Atkinson; Jonathan A. Atkinson; Craig J. Sturrock; Andrew B. Riche; W. Richard Whalley; Malcolm J. Hawkesford; Hannah V. Cooper; Sacha J. Mooney (Rhizosphere, 2023)

Lethal and Sub-lethal Implications of Sodium Chloride Exposure for Adult Unionid Mussel Species: Eurynia dilatata and Lasmigona costata - Erika A. Burton; Brian Atkinson; Joseph Salerno; Hufsa N. Khan; Ryan S. Prosser; Patricia L. Gillis (Archives of Environmental Contamination and Toxicology, 2023)
The elevated use of salt as a de-icing agent on roads in Canada is causing an increase in the chloride concentration of freshwater ecosystems. Freshwater Unionid mussels are a group of organisms that are sensitive to increases in chloride levels. Unionids have greater diversity in North America than anywhere else on Earth, but they are also one of the most imperiled groups of organisms. This underscores the importance of understanding the effect that increasing salt exposure has on these threatened species. There are more data on the acute toxicity of chloride to Unionids than on chronic toxicity. This study investigated the effect of chronic sodium chloride exposure on the survival and filtering activity of two Unionid species ( Eurynia dilatata, and Lasmigona costata ) and assessed the effect on the metabolome in L. costata hemolymph. The concentration causing mortality after 28 days of exposure was similar for E. dilatata (1893 mg Cl − /L) and L. costata (1903 mg Cl − /L). Significant changes in the metabolome of the L. costata hemolymph were observed for mussels exposed to non-lethal concentrations. For example, several phosphatidylethanolamines, several hydroxyeicosatetraenoic acids, pyropheophorbide-a, and alpha-linolenic acid were significantly upregulated in the hemolymph of mussels exposed to 1000 mg Cl − /L for 28 days. While no mortality occurred in the treatment, elevated metabolites in the hemolymph are an indicator of stress.

Broad-scale benthic habitat classification of the South Atlantic - Kirsty A. McQuaid; Amelia E.H. Bridges; Kerry L. Howell; Tiago B.R. Gandra; Vitor de Souza; Jock C. Currie; Oliver T. Hogg; Tabitha R.R. Pearman; James B. Bell; Lara J. Atkinson; Diane Baum; Jarbas Bonetti; et al. (Progress in Oceanography, 2023)

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Pathways to achieving nature-positive and carbon–neutral land use and food systems in Wales - Sarah M. Jones; Alison C. Smith; Nicholas Leach; Peter Henrys; Peter M. Atkinson; Paula A. Harrison (Regional Environmental Change, 2023)
Land use and its management can play a vital role in carbon sequestration, but trade-offs may exist with other objectives including food security and nature recovery. Using an integrated model (the FABLE calculator), four pathways, co-created with colleagues at the Welsh Government, towards achieving climate and biodiversity targets in Wales were explored: status quo, improvements on current trends, land sparing and land sharing. We found that continuing as usual will not be sufficient to meet Wales’s climate and biodiversity targets. In contrast, the land use and agricultural sector became a net carbon sink in both the land sparing and land sharing pathways, through high afforestation targets, peatland restoration, reducing food waste and moving towards a healthier diet. Whilst both pathways released land for biodiversity, the gains were greater in the land sharing pathway, which was also less dependent on optimistic assumptions concerning productivity improvements. The results demonstrate that alternative approaches to achieving nature-positive and carbon–neutral land use and food systems may be possible, but they come with stringent and transformative requirements for policy changes, with an integrated approach necessary to maximise benefits for climate, food and nature.

Long-term exposure to traffic-related air pollution and stroke: A systematic review and meta-analysis - P. Haddad; M. Kutlar Joss; J. Weuve; D. Vienneau; R. Atkinson; J. Brook; H. Chang; F. Forastiere; G. Hoek; R. Kappeler; F. Lurmann; S. Sagiv; et al. (International Journal of Hygiene and Environmental Health, 2023)

Associations between biomarkers of cellular senescence and physical function in humans: observations from the lifestyle interventions for elders (LIFE) study - Roger A. Fielding; Elizabeth J. Atkinson; Zaira Aversa; Thomas A. White; Amanda A. Heeren; Sara J. Achenbach; Michelle M. Mielke; Steven R. Cummings; Marco Pahor; Christiaan Leeuwenburgh; Nathan K. LeBrasseur (GeroScience, 2022)
Cellular senescence is a plausible mediator of age-associated declines in physical performance. To test this premise, we examined cross-sectional associations between circulating components of the senescence-associated secretory phenotype (SASP) and measures of physical function and muscle strength in 1377 older adults. We showed significant associations between multiple SASP proteins and the short physical performance battery (SPPB), its subcomponents (gait speed, balance, chair rise time), and 400-m walk time. Activin A, ICAM1, MMP7, VEGFA, and eotaxin showed strong associations based on gradient boost machine learning (GBM), and, when combined with other proteins, effectively identified participants at the greatest risk for mobility disability (SPPB score $$\le$$ ≤ 7). Senescence biomarkers were also associated with lower grip strength, and GBM identified PARC, ADAMTS13, and RANTES as top candidates in females, and MMP2, SOST, and MCP1 in males. These findings highlight an association between senescence biomarkers and physical performance in older adults. ClinicalTrials.gov Identifier: NCT01072500.

Massive circumpolar biomass of Southern Ocean zooplankton: Implications for food web structure, carbon export, and marine spatial planning - Guang Yang; Angus Atkinson; Evgeny A. Pakhomov; Simeon L. Hill; Marie‐Fanny Racault (Limnology and Oceanography, 2022)
With rapid, sector‐specific climatic changes impacting the Southern Ocean, we need circumpolar‐scale biomass data of its plankton taxa to improve food web models, blue carbon budgets and resource management. Here, we provide a new dataset on mesozooplankton biomass with 2909 records spanning the last 90 yr, and describe, in comparable carbon units, their circumpolar distribution alongside those of phytoplankton, Antarctic krill, and salps. With our datasets, we estimate total summer carbon biomasses for phytoplankton (36 MT), mesozooplankton (67 MT), krill (30 MT), and salps (1.7 MT). The mesozooplankton value is much higher than previously reported and, added to that of krill and salps, points to an enormous overall biomass of zooplankton in the Southern Ocean. This means that the pyramids of biomass are often inverted, with higher biomass of zooplankton than of phytoplankton. Such high biomasses suggest key roles of grazers in nutrient cycling and we estimate an export of ~ 50 Mt C yr −1 , solely from mortality of overwintering zooplankton that typically reside at depth. Deep lipid respiration (the lipid pump), for example, would increase this export even further. While inverted biomass pyramids prevailed at mid latitudes (50°–70°S), the balance of taxa differed regionally: for example, with biomass dominance by phytoplankton (highest latitudes and Pacific sector), mesozooplankton (Kerguelen Plateau), krill (north and east Scotia Sea), and salps (Crozet area). In light of contrasting climate change impacts between these sectors, we provide data that will underpin biogeochemical and food web models, blue carbon budgets, and the planning of marine protected areas.

Rare germline variants in the AXIN2 gene in families with colonic polyposis and colorectal cancer - James M. Chan; Mark Clendenning; Sharelle Joseland; Peter Georgeson; Khalid Mahmood; Romy Walker; Julia Como; Jihoon E. Joo; Susan Preston; Ryan A. Hutchinson; Bernard J. Pope; Andrew Metz; et al. (Familial Cancer, 2022)

Litter breakdown among intermittently connected and unconnected geographically isolated Wetlands: how nutrient inputs alter wetland function - Chelsea R. Smith; Stephen W. Golladay; Carla L. Atkinson; Brian A. Clayton (Wetlands, 2022)

Global synthesis reveals strong multifaceted effects of eucalypts on soils - Max Mallen‐Cooper; Joe Atkinson; Zoe A. Xirocostas; Baptiste Wijas; Giancarlo M. Chiarenza; Frederick A. Dadzie; David J. Eldridge (Global Ecology and Biogeography, 2022)
Aim Eucalypts have a widespread global distribution owing to their popularity for agroforestry and as environmental plantings. Despite an abundance of site‐specific evidence that eucalypts modify soils and soil processes, we lack a quantitative synthesis of their overall effects at the global scale. This limits our capacity to assess the likely impacts of future introductions in any given region of the world. Location Global. Time period 1986–2021. Major taxa studied Eucalyptus , Angophora and Corymbia . Methods We used a systematic search to derive a database of empirical data from 227 studies across 33 countries ( n effect size = 2,806) and tested three predictions about the effects of eucalypts on soil properties and whether these effects varied with plantation age and soil depth. Results Compared with (non‐eucalypt) native vegetation, eucalypts significantly reduced soil moisture, microbial abundance, nitrogen, cations and anions. Relative reductions in soil microbes and ions were stronger in older eucalypt plantations. A comparison of eucalypts with (non‐eucalypt) silvicultural and agropastoral systems revealed similar effects on most soil properties, although eucalypts tended to reduce potassium and enhance carbon to a greater extent than other managed systems. We found no consistent effects of eucalypts on soil pH. Main conclusions Our study provides the first extensive global meta‐analysis of the effects of eucalypts on soil properties and processes and demonstrates that effects are highly dependent on the community with which they are compared (i.e., natural or managed). In general, our findings reinforce the widely held belief that eucalypts deplete soil nutrients and dominate water resources. Understanding how eucalypts affect soils allows us to assess their global suitability for agroforestry, soil rehabilitation and soil carbon enhancement, while considering the potential environmental costs.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Terrestrial ecosystem restoration increases biodiversity and reduces its variability, but not to reference levels: A global meta‐analysis - Joe Atkinson; Lars A. Brudvig; Max Mallen‐Cooper; Shinichi Nakagawa; Angela T. Moles; Stephen P. Bonser (Ecology Letters, 2022)
Ecological restoration projects often have variable and unpredictable outcomes, and these can limit the overall impact on biodiversity. Previous syntheses have investigated restoration effectiveness by comparing average restored conditions to average conditions in unrestored or reference systems. Here, we provide the first quantification of the extent to which restoration affects both the mean and variability of biodiversity outcomes, through a global meta‐analysis of 83 terrestrial restoration studies. We found that, relative to unrestored (degraded) sites, restoration actions increased biodiversity by an average of 20%, while decreasing the variability of biodiversity (quantified by the coefficient of variation) by an average of 14%. As restorations aged, mean biodiversity increased and variability decreased relative to unrestored sites. However, restoration sites remained, on average, 13% below the biodiversity of reference (target) ecosystems, and were characterised by higher (20%) variability. The lower mean and higher variability in biodiversity at restored sites relative to reference sites remained consistent over time, suggesting that sources of variation (e.g. prior land use, restoration practices) have an enduring influence on restoration outcomes. Our results point to the need for new research confronting the causes of variability in restoration outcomes, and close variability and biodiversity gaps between restored and reference conditions.

Stepping stones towards Antarctica: Switch to southern spawning grounds explains an abrupt range shift in krill - Angus Atkinson; Simeon L. Hill; Christian S. Reiss; Evgeny A. Pakhomov; Gregory Beaugrand; Geraint A. Tarling; Guang Yang; Deborah K. Steinberg; Katrin Schmidt; Martin Edwards; Emilce Rombolá; Frances A. Perry (Global Change Biology, 2022)
Poleward range shifts are a global‐scale response to warming, but these vary greatly among taxa and are hard to predict for individual species, localized regions or over shorter (years to decadal) timescales. Moving poleward might be easier in the Arctic than in the Southern Ocean, where evidence for range shifts is sparse and contradictory. Here, we compiled a database of larval Antarctic krill, Euphausia superba and, together with an adult database, it showed how their range shift is out of step with the pace of warming. During a 70‐year period of rapid warming (1920s–1990s), distribution centres of both larvae and adults in the SW Atlantic sector remained fixed, despite warming by 0.5–1.0°C and losing sea ice. This was followed by a hiatus in surface warming and ice loss, yet during this period the distributions of krill life stages shifted greatly, by ~1000 km, to the south‐west. Understanding the mechanism of such step changes is essential, since they herald system reorganizations that are hard to predict with current modelling approaches. We propose that the abrupt shift was driven by climatic controls acting on localized recruitment hotspots, superimposed on thermal niche conservatism. During the warming hiatus, the Southern Annular Mode index continued to become increasingly positive and, likely through reduced feeding success for larvae, this led to a precipitous decline in recruitment from the main reproduction hotspot along the southern Scotia Arc. This cut replenishment to the northern portion of the krill stock, as evidenced by declining density and swarm frequency. Concomitantly, a new, southern reproduction area developed after the 1990s, reinforcing the range shift despite the lack of surface warming. New spawning hotspots may provide the stepping stones needed for range shifts into polar regions, so planning of climate‐ready marine protected areas should include these key areas of future habitat.

Substantial long‐term loss of alpha and gamma diversity of lake invertebrates in a landscape exposed to a drying climate - S. T. Atkinson; D. Cale; A. Pinder; J. M. Chambers; S. A. Halse; Belinda J. Robson (Global Change Biology, 2021)
Many regions across the globe are shifting to more arid climates. For shallow lakes, decreasing rainfall volume and timing, changing regional wind patterns and increased evaporation rates alter water regimes so that dry periods occur more frequently and for longer. Drier conditions may affect fauna directly and indirectly through altered physicochemical conditions in lakes. Although many studies have predicted negative effects of such changes on aquatic biodiversity, empirical studies demonstrating these effects are rare. Global warming has caused severe climatic drying in southwestern Australia since the 1970s, so we aimed to determine whether lakes in this region showed impacts on lake hydroperiod, water quality, and α, β and γ diversity of lake invertebrates from 1998 to 2011. Seventeen lakes across a range of salinities were sampled biennially in spring in the Wheatbelt and Great Southern regions of Western Australia. Multivariate analyses were used to identify changes in α, β and γ diversity and examine patterns in physicochemical data. Salinity and average rainfall partially explained patterns in invertebrate richness and assemblage composition. Climatic drying was associated with significant declines in lake depth, increased frequency of dry periods, and reduced α and γ diversity (γ declined from ~300 to ~100 taxa from 1998 to 2011 in the 17 wetlands). In contrast, β diversity remained consistently high, because each lake retained a distinct fauna. Mean α diversity per‐lake declined both in lakes that dried and lakes that did not dry out, but lakes which retained a greater proportion of their maximum depth retained more α diversity. Accumulated losses in α diversity caused the decline in γ diversity likely through shrinking habitat area, fewer stepping stones for dispersal and loss of specific habitat types. Biodiversity loss is thus likely from lakes in drying regions globally. Management actions will need to sustain water depth in lakes to prevent biodiversity loss.

Increasing nutrient stress reduces the efficiency of energy transfer through planktonic size spectra - Angus Atkinson; Martin K.S. Lilley; Andrew G. Hirst; Andrea J. McEvoy; Glen A. Tarran; Claire Widdicombe; Elaine S. Fileman; E. Malcolm S. Woodward; Katrin Schmidt; Tim J. Smyth; Paul J. Somerfield (Limnology and Oceanography, 2021)
Size‐spectral approaches quantify the efficiency of energy transfer through food webs, but theory and field studies disagree over how changes in temperature, nutrients, and extreme weather impact on this efficiency. We address this at two scales: via 6 years of weekly sampling of the plankton size spectrum at the Plymouth L4 shelf sea site, and via a new, global‐scale, meta‐analysis of aquatic size spectra. The time series showed that with summertime nutrient starvation, the energy transfer efficiency from picoplankton to macroplankton decreased (i.e., steepening slopes of the size spectra). This reflected increasing dominance by small cells and their microbial consumers. The extreme storms in winter 2013/2014 caused high metazoan mortality, steep size‐spectral slopes, and reduced plankton biomass. However, recovery was within months, demonstrating an inbuilt resilience of the system. Both L4 and our meta‐analysis showed steep slopes of normalized size spectra (median −1.11). This reflects much lower values, either of trophic transfer efficiency (3.5%) or predator–prey mass ratio (569), compared to commonly quoted values. Results from the meta‐analysis further showed that to represent energy transfer faithfully, size spectra are best constructed in units of carbon mass and not biovolume, and span a mass range of > 10 7 . When this range is covered, both the meta‐analysis and time series show a dome‐shaped relationship between spectral slopes and plankton biomass, with steepening slopes under increasingly oligotrophic and eutrophic conditions. This suggests that ocean warming could decrease the efficiency of energy transfer through pelagic food webs via indirect effects of increasing stratification and nutrient starvation.

Filter-feeders have differential bottom-up impacts on green and brown food webs - Carla L. Atkinson; Halvor M. Halvorson; Kevin A. Kuehn; Monica Winebarger; Ansley Hamid; Matthew N. Waters (Oecologia, 2021)

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

Increasing picocyanobacteria success in shelf waters contributes to long‐term food web degradation - Katrin Schmidt; Antony J. Birchill; Angus Atkinson; Robert J. W. Brewin; James R. Clark; Anna E. Hickman; David G. Johns; Maeve C. Lohan; Angela Milne; Silvia Pardo; Luca Polimene; Tim J. Smyth; et al. (Global Change Biology, 2020)
Continental margins are disproportionally important for global primary production, fisheries and CO 2 uptake. However, across the Northeast Atlantic shelves, there has been an ongoing summertime decline of key biota—large diatoms, dinoflagellates and copepods—that traditionally fuel higher tropic levels such as fish, sea birds and marine mammals. Here, we combine multiple time series with in situ process studies to link these declines to summer nutrient stress and increasing proportions of picophytoplankton that can comprise up to 90% of the combined pico‐ and nanophytoplankton biomass in coastal areas. Among the pico‐fraction, it is the cyanobacterium Synechococcus that flourishes when iron and nitrogen resupply to surface waters are diminished. Our field data show how traits beyond small size give Synechococcus a competitive edge over pico‐ and nanoeukaryotes. Key is their ability to grow at low irradiances near the nutricline, which is aided by their superior light‐harvesting system and high affinity to iron. However, minute size and lack of essential biomolecules (e.g. omega‐3 polyunsaturated fatty acids and sterols) render Synechococcus poor primary producers to sustain shelf sea food webs efficiently. The combination of earlier spring blooms and lower summer food quantity and quality creates an increasing period of suboptimal feeding conditions for zooplankton at a time of year when their metabolic demand is highest. We suggest that this nutrition‐related mismatch has contributed to the widespread, ~50% decline in summer copepod abundance we observe over the last 60 years. With Synechococcus clades being prominent from the tropics to the Arctic and their abundances increasing worldwide, our study informs projections of future food web dynamics in coastal and shelf areas where droughts and stratification lead to increasing nutrient starvation of surface waters.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Temperature–Induced Hatch Failure and Nauplii Malformation in Antarctic Krill - Frances A. Perry; So Kawaguchi; Angus Atkinson; Sévrine F. Sailley; Geraint A. Tarling; Daniel J. Mayor; Cathy H. Lucas; R. King; A. Cooper (Frontiers in Marine Science, 2020)

Lifeform indicators reveal large‐scale shifts in plankton across the North‐West European shelf - Jacob Bedford; Clare Ostle; David G. Johns; Angus Atkinson; Mike Best; Eileen Bresnan; Margarita Machairopoulou; Carolyn A. Graves; Michelle Devlin; Alex Milligan; Sophie Pitois; Adam Mellor; et al. (Global Change Biology, 2020)
Increasing direct human pressures on the marine environment, coupled with climate‐driven changes, is a concern to marine ecosystems globally. This requires the development and monitoring of ecosystem indicators for effective management and adaptation planning. Plankton lifeforms (broad functional groups) are sensitive indicators of marine environmental change and can provide a simplified view of plankton biodiversity, building an understanding of change in lower trophic levels. Here, we visualize regional‐scale multi‐decadal trends in six key plankton lifeforms as well as their correlative relationships with sea surface temperature (SST). For the first time, we collate trends across multiple disparate surveys, comparing the spatially and temporally extensive Continuous Plankton Recorder (CPR) survey (offshore) with multiple long‐term fixed station‐based time‐series (inshore) from around the UK coastline. These analyses of plankton lifeforms showed profound long‐term changes, which were coherent across large spatial scales. For example, ‘diatom’ and ‘meroplankton’ lifeforms showed strong alignment between surveys and coherent regional‐scale trends, with the 1998–2017 decadal average abundance of meroplankton being 2.3 times that of 1958–1967 for CPR samples in the North Sea. This major, shelf‐wide increase in meroplankton correlated with increasing SSTs, and contrasted with a general decrease in holoplankton (dominated by small copepods), indicating a changing balance of benthic and pelagic fauna. Likewise, inshore‐offshore gradients in dinoflagellate trends, with contemporary increases inshore contrasting with multi‐decadal decreases offshore (approx. 75% lower decadal mean abundance), urgently require the identification of causal mechanisms. Our lifeform approach allows the collation of many different data types and time‐series across the NW European shelf, providing a crucial evidence base for informing ecosystem‐based management, and the development of regional adaptation plans.

Renewable energy development threatens many globally important biodiversity areas - Jose A. Rehbein; James E. M. Watson; Joe L. Lane; Laura J. Sonter; Oscar Venter; Scott C. Atkinson; James R. Allan (Global Change Biology, 2020)
Transitioning from fossil fuels to renewable energy is fundamental for halting anthropogenic climate change. However, renewable energy facilities can be land‐use intensive and impact conservation areas, and little attention has been given to whether the aggregated effect of energy transitions poses a substantial threat to global biodiversity. Here, we assess the extent of current and likely future renewable energy infrastructure associated with onshore wind, hydropower and solar photovoltaic generation, within three important conservation areas: protected areas (PAs), Key Biodiversity Areas (KBAs) and Earth's remaining wilderness. We identified 2,206 fully operational renewable energy facilities within the boundaries of these conservation areas, with another 922 facilities under development. Combined, these facilities span and are degrading 886 PAs, 749 KBAs and 40 distinct wilderness areas. Two trends are particularly concerning. First, while the majority of historical overlap occurs in Western Europe, the renewable electricity facilities under development increasingly overlap with conservation areas in Southeast Asia, a globally important region for biodiversity. Second, this next wave of renewable energy infrastructure represents a ~30% increase in the number of PAs and KBAs impacted and could increase the number of compromised wilderness areas by ~60%. If the world continues to rapidly transition towards renewable energy these areas will face increasing pressure to allow infrastructure expansion. Coordinated planning of renewable energy expansion and biodiversity conservation is essential to avoid conflicts that compromise their respective objectives.

India’s contribution to mitigating the impacts of climate change through vegetation management - J. Dash; M. D. Behera; C. Jeganathan; C. S. Jha; S. Sharma; R. Lucas; A. A. Khuroo; A. Harris; P. M. Atkinson; D. S. Boyd; C. P. Singh; M. P. Kale; et al. (Tropical Ecology, 2020)

Navigating Institutional Challenges: Design to Enable Community Participation in Social Learning for Freshwater Planning - James A. Turner; Will Allen; Caroline Fraser; Andrew Fenemor; Akiko Horita; Toni White; Lan Chen; Maggie Atkinson; Michelle Rush (Environmental Management, 2020)

Resilience of the Copepod Oithona similis to Climatic Variability: Egg Production, Mortality, and Vertical Habitat Partitioning - Louise Elisabeth Cornwell; Elaine S. Fileman; John T. Bruun; Andrew Garwood Hirst; Glen Adam Tarran; Helen S. Findlay; Ceri Lewis; Timothy James Smyth; A. J. McEvoy; A. Atkinson (Frontiers in Marine Science, 2020)

Pregnancy rate and biomarker validations from the blubber of eastern North Pacific blue whales - Shannon Atkinson; Diane Gendron; Trevor A. Branch; Kendall L. Mashburn; Valentina Melica; Luis E. Enriquez‐Paredes; Robert L. Brownell (Marine Mammal Science, 2020)
Hormonal biomarkers are useful indicators of mammalian reproductive and metabolic states. The present study validated and applied the use of progesterone and cortisol blubber assays for studies of blue whales from the Gulf of California, Mexico. In a validation study for pregnancy detection, blubber progesterone concentrations were correlated with pregnancy status for four female blue whales: three resighted with a calf the year following sampling and the fourth stranded with a fetus. The progesterone concentrations were significantly higher than those measured in juvenile whales ( n = 3). In the application study, blubber samples from blue whales (51 noncalf females, 2 female calves, 48 noncalf males, and 1 male calf) with known sighting histories were analyzed. Putative pregnant females had elevated progesterone concentrations. Cortisol concentrations did not differ between male and female blue whales, or among females in different reproductive classes. After correcting for uncertain ages, hence maturity status, the pregnancy rate of noncalf females was 33.4% (95% CI 32.2%–34.3%). Although interpretation of hormone biomarkers must consider all physiological states that may influence progesterone concentrations, these results demonstrate the utility of pairing hormone biomarkers with sighting histories to help assess environmental or anthropogenic impacts on reproduction in blue whales.

Dose evaluation of intravenous metamizole (dipyrone) in infants and children: a prospective population pharmacokinetic study - Victoria C. Ziesenitz; Frédérique Rodieux; Andrew Atkinson; Carole Borter; Julia A. Bielicki; Manuel Haschke; Urs Duthaler; Fabio Bachmann; Thomas O. Erb; Nicolas Gürtler; Stefan Holland-Cunz; Johannes N. van den Anker; et al. (European Journal of Clinical Pharmacology, 2019)

Behavioral repertoire assessment of Bengal tigers (Panthera tigris) with focus on thermoregulatory behavior - Judith A. Stryker; Jim L. Atkinson; Robert D. Brown; David Barney; J. Andy B. Robinson; Jay Duncan; Esther J. Finegan (International Journal of Biometeorology, 2019)

Nutrient recycling by insect and fish communities in high-elevation tropical streams - Carla L. Atkinson; Alexander V. Alexiades; Keeley L. MacNeill; Andrea C. Encalada; Steve A. Thomas; Alexander S. Flecker (Hydrobiologia, 2019)

Phylogeny of Mesoamerican freshwater mussels and a revised tribe‐level classification of the Ambleminae - John M. Pfeiffer; Carla L. Atkinson; Ashley E. Sharpe; Krista A. Capps; Kitty F. Emery; Lawrence M. Page (Zoologica Scripta, 2019)
Evolutionary and ecological hypotheses of the freshwater mussel subfamily Ambleminae are intensely geographically biased—a consequence of the complete exclusion of Mesoamerican taxa in phylogenetic reconstructions of the clade. We set out to integrate a portion of the Mesoamerican freshwater mussel assemblage into existing hypotheses of amblemine classification and evolution by generating a molecular phylogeny that includes four previously unsampled Mesoamerican genera and nine species endemic to that region. Given the traditionally hypothesized affinity to Nearctic mussels and the understanding that classification should reflect common ancestry, we predicted that (a) Mesoamerican genera would be recovered as members of the recognized tribes of the Ambleminae, and (b) genera would be supported as monophyletic. The mutilocus phylogeny (COI + 28S + 16S) reported herein does not fully support either of those hypotheses. Neither Cyrtonaias nor Psorula were supported as monophyletic and we predict several other Mesoamerica genera are also non‐monophyletic. The reconstructed phylogeny recovered four independent lineages of Mesoamerican freshwater mussels and these clades are distributed across the phylogeny of the Ambleminae, including the tribe Quadrulini ( Megalonaias ), Lampsilini (two lineages: Cyrtonaias explicata / Sphenonaias microdon , and Pachynaias ), and a previously unrecognized, exclusively Mesoamerican and Rio Grande clade consisting of the genera Psoronaias , Psorula and Popenaias . The latter clade possesses several morphological characteristics that distinguish it from its sister taxon, tribe Lampsilini, and we recognize this newly identified Mesoamerican clade as a fifth tribe of the Ambleminae attributable to the Popenaiadini Heard & Guckert, 1970. This revised classification more completely recognizes the suprageneric diversity of the Ambleminae.

Determinants of food resource assimilation by stream insects along a tropical elevation gradient - Carla L. Atkinson; Andrea C. Encalada; Amanda T. Rugenski; Steve A. Thomas; Andrea Landeira-Dabarca; N. LeRoy Poff; Alexander S. Flecker (Oecologia, 2018)

Modelling the distribution of hard seabed using calibrated multibeam acoustic backscatter data in a tropical, macrotidal embayment: Darwin Harbour, Australia - P. Justy W. Siwabessy; Maggie Tran; Kim Picard; Brendan P. Brooke; Zhi Huang; Neil Smit; David K. Williams; William A. Nicholas; Scott L. Nichol; Ian Atkinson (Marine Geophysical Research, 2018)

Localised cutaneous microvascular adaptation to exercise training in humans - Ceri L. Atkinson; Howard H. Carter; Dick H. J. Thijssen; Gurpreet K. Birk; N. Timothy Cable; David A. Low; Floortje Kerstens; Iris Meeuwis; Ellen A. Dawson; Daniel J. Green (European Journal of Applied Physiology, 2018)

Mapping paddy rice fields by applying machine learning algorithms to multi-temporal Sentinel-1A and Landsat data - Alex O. Onojeghuo; George A. Blackburn; Qunming Wang; Peter M. Atkinson; Daniel Kindred; Yuxin Miao (International Journal of Remote Sensing, 2018)

Representation of mid‐latitude North American coastal storm activity by six global reanalyses - Katherine A. Pingree‐Shippee; Francis W. Zwiers; David E. Atkinson (International Journal of Climatology, 2018)
Extratropical cyclones often produce extreme and hazardous weather conditions, such as high winds, heavy precipitation, blizzard conditions, and flooding, all of which have detrimental environmental/physical and socio‐economic impacts. Furthermore, storm interaction with the ocean produces additional hazards, with major local impacts, including inundation and coastal erosion. The North American west coast is influenced by the North Pacific storm track and by ‘atmospheric river’ events while the east coast is particularly influenced by winter storms that track along two favoured routes: the St. Lawrence Valley and the Eastern Seaboard. Reanalysis provides an invaluable tool for studying the characteristics of storm events that are identified as causing the most severe impacts. However, reanalysis products differ substantially in spatial resolution, model physics, assimilation approach, and the data that are assimilated. This study evaluates the representation of storm activity along the mid‐latitude North American coastlines by six global reanalyses: NCEP‐1, NCEP‐2, ERA‐Interim, Modern‐Era Retrospective analysis for Research and Applications (MERRA), Climate Forecast System Reanalysis (CFSR), and Twentieth Century Reanalysis Version 2 (20CR). Storm activity representation is evaluated at annual and seasonal timescales (JFM, AMJ, JAS, OND, and ‘extended winter’ ONDFM) during the 1979–2010 time period through comparison with selected meteorological stations using single‐point surface pressure‐based proxies of extratropical storm activity. Stations are selected on the basis of record length, reporting frequency, coastal proximity, and relatively uniform spatial distribution. Comparisons are made using data extracted from the reanalysis grid box centre that is closest to each selected station. All reanalyses are found to successfully represent most aspects of mid‐latitude North American coastal strong storm activity, annually and seasonally, along both coasts. Nevertheless, ERA‐Interim, MERRA, and CFSR provide the better representations of mid‐latitude North American coastal strong storm activity, with ERA‐Interim performing best overall.

The potential role of Antarctic krill faecal pellets in efficient carbon export at the marginal ice zone of the South Orkney Islands in spring - A. Belcher; G. A. Tarling; C. Manno; A. Atkinson; P. Ward; G. Skaret; S. Fielding; S. A. Henson; R. Sanders (Polar Biology, 2017)

Patterns and trends of pediatric bloodstream infections: a 7-year surveillance study - N. Buetti; A. Atkinson; L. Kottanattu; J. Bielicki; J. Marschall; A. Kronenberg (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Occurrence of two novel actinospore types (Cnidaria: Myxosporea) in Brazilian fish farms, and the creation of a novel actinospore collective group, Seisactinomyxon - Tiago Milanin; Stephen D. Atkinson; Márcia R.M. Silva; Roberto G. Alves; Antônio A.M. Maia; Edson A. Adriano (Acta Parasitologica, 2017)
The involvement of oligochaetes in the life cycles of fresh water myxozoan parasites in Brazil was investigated. Of 333 oligochaetes collected in a fish farm in the State of São Paulo, three (0.9%) released Aurantiactinomyxon type spores. From 86 worms collected in a fish farm in Mato Grosso do Sul State, 1 (0.9%) released actinospores with a novel morphology for which we propose the name Seisactinomyxon. Infected oligochaetes were identified by morphology: all belonged to family Naididae, with

Ontogenetic body‐mass scaling of nitrogen excretion relates to body surface area in diverse pelagic invertebrates - A. G. Hirst; M. K. S. Lilley; D. S. Glazier; D. Atkinson (Limnology and Oceanography, 2017)
Many physiological and ecological processes depend on body size and the supply of limiting nutrients. Hence, it is important to derive quantitative predictions based on a mechanistic understanding of the influence of body size on metabolic rate and on the ratios of consumed to excreted elements. Among diverse pelagic invertebrates that change shape during ontogeny, recent analysis has demonstrated a significant positive correlation between the body‐mass allometry of respiration rates (measured as the ontogenetic body mass‐scaling exponent b R ) and the allometry of body surface area ( b A , as predicted from body‐shape changes using a Euclidean model). As many pelagic invertebrates use a large portion of their external body surface for both resource uptake and waste excretion, we predicted that body‐mass scaling exponents for rates of excretion of soluble N ( b N ) should also then relate to the degree of body‐shape change during growth. We tested this hypothesis using literature data on b N for 39 species of pelagic invertebrates across five different phyla, and find strong support: b N is significantly positively correlated with predicted b A , whilst also co‐varying with b R . Intraspecific differences between b N and b R values reveal ontogenetic shifts in the ratio of O 2 ‐consumed to N‐excreted. We suggest that a variety of factors, including adaptive developmental shifts in the relative anabolism and catabolism of proteins and lipids, may cause these shifts in consumption–excretion ratios. Diverse pelagic invertebrates that dominate vast open water ecosystems falsify the predictions of general metabolic scaling theories built upon resource‐transport networks, but support predictions of surface‐area dependent theory.

Reference Intervals of Mineral Elements in Plasma of Anesthetized Free-Ranging Adult Females of South American Sea Lion, Otaria flavescens - Paula S. Polizzi; L. N. Chiodi Boudet; A. Ponce de León; M. Quiroga; D. H. Rodríguez; S. Atkinson; M. S. Gerpe (Biological Trace Element Research, 2016)

Seasonal nutritional status in Norway lobsters, Nephrops norvegicus (L.): are females nutritionally compromised over the winter? - Andrew J. R. Watts; Amaya Albalat; Ian P. Smith; Robert J. A. Atkinson; Douglas M. Neil (Marine Biology Research, 2016)

Epidemiological risk factors associated with inflammatory breast cancer subtypes - Rachel L. Atkinson; Randa El-Zein; Vicente Valero; Anthony Lucci; Therese B. Bevers; Tamer Fouad; Weiqin Liao; Naoto T. Ueno; Wendy A. Woodward; Abenaa M. Brewster (Cancer Causes & Control, 2016)

Will a warmer and wetter future cause extinction of native H awaiian forest birds? - Wei Liao; Oliver Elison Timm; Chunxi Zhang; Carter T. Atkinson; Dennis A. LaPointe; Michael D. Samuel (Global Change Biology, 2015)
Isolation of the Hawaiian archipelago produced a highly endemic and unique avifauna. Avian malaria ( Plasmodium relictum ), an introduced mosquito‐borne pathogen, is a primary cause of extinctions and declines of these endemic honeycreepers. Our research assesses how global climate change will affect future malaria risk and native bird populations. We used an epidemiological model to evaluate future bird–mosquito–malaria dynamics in response to alternative climate projections from the Coupled Model Intercomparison Project. Climate changes during the second half of the century accelerate malaria transmission and cause a dramatic decline in bird abundance. Different temperature and precipitation patterns produce divergent trajectories where native birds persist with low malaria infection under a warmer and dryer projection ( RCP 4.5), but suffer high malaria infection and severe reductions under hot and dry ( RCP 8.5) or warm and wet (A1B) futures. We conclude that future global climate change will cause significant decreases in the abundance and diversity of remaining Hawaiian bird communities. Because these effects appear unlikely before mid‐century, natural resource managers have time to implement conservation strategies to protect this unique avifauna from further decimation. Similar climatic drivers for avian and human malaria suggest that mitigation strategies for Hawai'i have broad application to human health.

Seismically induced landslide hazard and exposure modelling in Southern California based on the 1994 Northridge, California earthquake event - M. E. A. Budimir; P. M. Atkinson; H. G. Lewis (Landslides, 2015)

Impact of handgrip exercise intensity on brachial artery flow-mediated dilation - Ceri L. Atkinson; Howard H. Carter; Ellen A. Dawson; Louise H. Naylor; Dick H. J. Thijssen; Daniel J. Green (European Journal of Applied Physiology, 2015)

Crop rotational diversity enhances belowground communities and functions in an agroecosystem - L. K. Tiemann; A. S. Grandy; E. E. Atkinson; E. Marin‐Spiotta; M. D. McDaniel (Ecology Letters, 2015)
Biodiversity loss, an important consequence of agricultural intensification, can lead to reductions in agroecosystem functions and services. Increasing crop diversity through rotation may alleviate these negative consequences by restoring positive aboveground–belowground interactions. Positive impacts of aboveground biodiversity on belowground communities and processes have primarily been observed in natural systems. Here, we test for the effects of increased diversity in an agroecosystem, where plant diversity is increased over time through crop rotation. As crop diversity increased from one to five species, distinct soil microbial communities were related to increases in soil aggregation, organic carbon, total nitrogen, microbial activity and decreases in the carbon‐to‐nitrogen acquiring enzyme activity ratio. This study indicates positive biodiversity–function relationships in agroecosystems, driven by interactions between rotational and microbial diversity. By increasing the quantity, quality and chemical diversity of residues, high diversity rotations can sustain soil biological communities, with positive effects on soil organic matter and soil fertility.

The Local Early Action Planning (LEAP) Tool: Enhancing Community-Based Planning for a Changing Climate - Supin Wongbusarakum; Meghan Gombos; Britt-Anne A. Parker; Catherine A. Courtney; Scott Atkinson; Willy Kostka (Coastal Management, 2015)

Erratum to: Earthquake-and-landslide events are associated with more fatalities than earthquakes alone - M. E. A. Budimir; P. M. Atkinson; H. G. Lewis (Natural Hazards, 2015)

A systematic review of landslide probability mapping using logistic regression - M. E. A. Budimir; P. M. Atkinson; H. G. Lewis (Landslides, 2015)

Elucidating the impact of temperature variability and extremes on cereal croplands through remote sensing - John M. A. Duncan; Jadunandan Dash; Peter M. Atkinson (Global Change Biology, 2015)
Remote sensing‐derived wheat crop yield‐climate models were developed to highlight the impact of temperature variation during thermo‐sensitive periods (anthesis and grain‐filling; TSP ) of wheat crop development. Specific questions addressed are: can the impact of temperature variation occurring during the TSP on wheat crop yield be detected using remote sensing data and what is the impact? Do crop critical temperature thresholds during TSP exist in real world cropping landscapes? These questions are tested in one of the world's major wheat breadbaskets of Punjab and Haryana, north‐west India. Warming average minimum temperatures during the TSP had a greater negative impact on wheat crop yield than warming maximum temperatures. Warming minimum and maximum temperatures during the TSP explain a greater amount of variation in wheat crop yield than average growing season temperature. In complex real world cereal croplands there was a variable yield response to critical temperature threshold exceedance, specifically a more pronounced negative impact on wheat yield with increased warming events above 35 °C. The negative impact of warming increases with a later start‐of‐season suggesting earlier sowing can reduce wheat crop exposure harmful temperatures. However, even earlier sown wheat experienced temperature‐induced yield losses, which, when viewed in the context of projected warming up to 2100 indicates adaptive responses should focus on increasing wheat tolerance to heat. This study shows it is possible to capture the impacts of temperature variation during the TSP on wheat crop yield in real world cropping landscapes using remote sensing data; this has important implications for monitoring the impact of climate change, variation and heat extremes on wheat croplands.

Influence of nocturnal and daytime sleep on initial orthostatic hypotension - N. C. S. Lewis; H. Jones; P. N. Ainslie; A. Thompson; K. Marrin; G. Atkinson (European Journal of Applied Physiology, 2015)

Feeding rates and prey selectivity of planktonic decapod larvae in the Western English Channel - Elaine S. Fileman; Penelope K. Lindeque; Rachel A. Harmer; Claudia Halsband; Angus Atkinson (Marine Biology, 2014)

Three-dimensional hydrofacies assemblages in ice-contact/proximal sediments forming a heterogeneous ‘hybrid’ hydrostratigraphic unit in central Illinois, USA - Lisa A. Atkinson; Martin Ross; Andrew J. Stumpf (Hydrogeology Journal, 2014)

Effects of two contrasting canopy manipulations on growth and water use of London plane (Platanus x acerifolia) trees - Neil A. Hipps; Michael J. Davies; Joel M. Dunn; Howard Griffiths; Christopher J. Atkinson (Plant and Soil, 2014)

Changing climate and the altitudinal range of avian malaria in the Hawaiian Islands – an ongoing conservation crisis on the island of Kaua'i - Carter T. Atkinson; Ruth B. Utzurrum; Dennis A. Lapointe; Richard J. Camp; Lisa H. Crampton; Jeffrey T. Foster; Thomas W. Giambelluca (Global Change Biology, 2014)
Transmission of avian malaria in the Hawaiian Islands varies across altitudinal gradients and is greatest at elevations below 1500 m where both temperature and moisture are favorable for the sole mosquito vector, Culex quinquefasciatus , and extrinsic sporogonic development of the parasite, Plasmodium relictum . Potential consequences of global warming on this system have been recognized for over a decade with concerns that increases in mean temperatures could lead to expansion of malaria into habitats where cool temperatures currently limit transmission to highly susceptible endemic forest birds. Recent declines in two endangered species on the island of Kaua'i, the ‘Akikiki ( Oreomystis bairdi ) and ‘Akeke'e ( Loxops caeruleirostris ), and retreat of more common native honeycreepers to the last remaining high elevation habitat on the Alaka'i Plateau suggest that predicted changes in disease transmission may be occurring. We compared prevalence of malarial infections in forest birds that were sampled at three locations on the Plateau during 1994–1997 and again during 2007–2013, and also evaluated changes in the occurrence of mosquito larvae in available aquatic habitats during the same time periods. Prevalence of infection increased significantly at the lower (1100 m, 10.3% to 28.2%), middle (1250 m, 8.4% to 12.2%), and upper ends of the Plateau (1350 m, 2.0% to 19.3%). A concurrent increase in detections of Culex larvae in aquatic habitats associated with stream margins indicates that populations of the vector are also increasing. These increases are at least in part due to local transmission because overall prevalence in Kaua'i ‘Elepaio ( Chasiempis sclateri ), a sedentary native species, has increased from 17.2% to 27.0%. Increasing mean air temperatures, declining precipitation, and changes in streamflow that have taken place over the past 20 years are creating environmental conditions throughout major portions of the Alaka'i Plateau that support increased transmission of avian malaria.

Earthquake-and-landslide events are associated with more fatalities than earthquakes alone - M. E. A. Budimir; P. M. Atkinson; H. G. Lewis (Natural Hazards, 2014)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Exploring the spatio-temporal relationship between two key aeroallergens and meteorological variables in the United Kingdom - Nabaz Khwarahm; Jadunandan Dash; Peter M. Atkinson; R. M. Newnham; C. A. Skjøth; B. Adams-Groom; Eric Caulton; K. Head (International Journal of Biometeorology, 2014)

Repeated core temperature elevation induces conduit artery adaptation in humans - Howard H. Carter; Angela L. Spence; Ceri L. Atkinson; Christopher J. A. Pugh; Louise H. Naylor; Daniel J. Green (European Journal of Applied Physiology, 2014)

Erratum to: Dissolved inorganic carbon and total alkalinity of a Hawaiian fringing reef: chemical techniques for monitoring the effects of ocean acidification on coral reefs - C. A. Lantz; M. J. Atkinson; C. W. Winn; S. E. Kahng (Coral Reefs, 2014)

Dissolved inorganic carbon and total alkalinity of a Hawaiian fringing reef: chemical techniques for monitoring the effects of ocean acidification on coral reefs - C. A. Lantz; M. J. Atkinson; C. W. Winn; S. E. Kahng (Coral Reefs, 2014)

An intra-specific linkage map of lettuce (Lactuca sativa) and genetic analysis of postharvest discolouration traits - Laura D. Atkinson; Leah K. McHale; María José Truco; Howard W. Hilton; James Lynn; Johan W. Schut; Richard W. Michelmore; Paul Hand; David A. C. Pink (Theoretical and Applied Genetics, 2013)

Synthesis and evaluation of p-N,N-dialkyl substituted chalcones as anti-cancer agents - Grady Nelson; Mohammad A. Alam; Tyler Atkinson; Shirisha Gurrapu; J. Sravan Kumar; Chris Bicknese; Joseph L. Johnson; Michael Williams (Medicinal Chemistry Research, 2013)

Nematode 18S rRNA gene is a reliable tool for environmental biosafety assessment of transgenic banana in confined field trials - R. Nakacwa; A. Kiggundu; H. Talwana; J. Namaganda; C. Lilley; W. Tushemereirwe; H. Atkinson (Transgenic Research, 2013)

Cooperation between scientists, NGOs and industry in support of sustainable fisheries: the South African hake Merluccius spp. trawl fishery experience a - J. G. Field; C. G. Attwood; A. Jarre; K. Sink; L. J. Atkinson; S. Petersen (Journal of Fish Biology, 2013)
This paper examines the increasingly close interaction between natural and social scientists, non‐governmental organizations (NGO) and industry, in pursuit of responsible ecosystem‐based management of fisheries. South Africa has committed to implementing an ecosystem approach to fisheries management. Management advice stems from multi‐stakeholder representation on government‐led scientific and management working groups. In the hake Merluccius capensis and Merluccius paradoxus fishery, the primary management measure is an annual total allowable catch ( TAC ), the level of which is calculated using a management procedure ( MP ) that is revised approximately every 4 years. Revision of the MP is a consultative process involving most stakeholders, and is based on simulation modelling of projected probable scenarios of resource and fishery dynamics under various management options. NGOs , such as the Worldwide Fund for Nature in South Africa (WWF‐SA), have played an important role in influencing consumers, the fishing industry and government to develop responsible fishing practices that minimize damage to marine ecosystems. Cooperation between industry, government and scientists has helped to improve sustainability and facilitated the meeting of market‐based incentives for more responsible fisheries. Research includes ecosystem modelling, spatial analysis and ecosystem risk assessment with increasing research focus on social and economic aspects of the fishery. A four‐year cooperative experiment to quantify the effect of trawling on benthic community structure is being planned. The food requirements of top predators still need to be included in the TAC ‐setting formulae and more social and economic research is needed. This paper also demonstrates how NGO initiatives such as Marine Stewardship Council certification and the Southern African Sustainable Seafood Initiative, a traffic light system of classifying seafood for consumers, have contributed to responsible fishing practices, increased ecosystem research and public awareness. This fishery appears to have a good future, provided that the monitoring, control and surveillance systems continue to function, TACs remain within ecologically sustainable limits and the effective collaboration between government, industry, scientists and NGOs continues to drive positive change.

Sex hormones and skeletal muscle weakness - Sarianna Sipilä; Marco Narici; Michael Kjaer; Eija Pöllänen; Ross A. Atkinson; Mette Hansen; Vuokko Kovanen (Biogerontology, 2013)

Conflicting and Complementary Ethics of Animal Welfare Considerations in Reintroductions - LAUREN A. HARRINGTON; AXEL MOEHRENSCHLAGER; MERRYL GELLING; ROB P. D. ATKINSON; JOELENE HUGHES; DAVID W. MACDONALD (Conservation Biology, 2013)
Despite differences in focus, goals, and strategies between conservation biology and animal welfare, both are inextricably linked in many ways, and greater consideration of animal welfare, although important in its own right, also has considerable potential to contribute to conservation success. Nevertheless, animal welfare and animal ethics are not always considered explicitly within conservation practice. We systematically reviewed the recent scientific peer‐reviewed and online gray literature on reintroductions of captive‐bred and wild‐caught animals (mammals, birds, amphibians, and reptiles) to quantify the occurrence of animal welfare issues. We considered monitoring that could be indicative of the animal's welfare status and supportive management actions that could improve animal welfare (regardless of whether the aim was explicitly animal‐welfare orientated). Potential welfare issues (of variable nature and extent) were recorded in 67% of 199 projects reviewed; the most common were mortality >50%, dispersal or loss of animals, disease, and human conflict. Most (>70%) projects monitored survival, 18% assessed body condition, and 2% monitored stress levels. Animal welfare, explicitly, was referred to in 6% of projects. Supportive actions, most commonly use of on‐site prerelease pens and provision of supplemental food or water, were implemented in 79% of projects, although the extent and duration of support varied. Practitioners can address animal‐welfare issues in reintroductions by considering the potential implications for individual animals at all stages of the release process using the decision tree presented. We urge practitioners to report potential animal‐welfare issues, describe mitigation actions, and evaluate their efficacy to facilitate transparent evaluation of common moral dilemmas and to advance communal strategies for dealing with them. Currently, comparative mortality rates, health risks, postrelease stress, effectiveness of supportive measures, and behavior of individuals warrant further research to improve animal welfare in reintroductions and to increase success of such projects. Ética Conflictiva y Complementaria al Considerar el Bienestar Animal en Reintroducciones

Structural, kinetic and computational investigation of Vitis vinifera DHDPS reveals new insight into the mechanism of lysine-mediated allosteric inhibition - Sarah C. Atkinson; Con Dogovski; Matthew T. Downton; Peter E. Czabotar; Renwick C. J. Dobson; Juliet A. Gerrard; John Wagner; Matthew A. Perugini (Plant Molecular Biology, 2013)

Analysing temporal trends in the Indian Summer Monsoon and its variability at a fine spatial resolution - J. M. A. Duncan; J. Dash; P. M. Atkinson (Climatic Change, 2013)

An enzyme activity capable of endotransglycosylation of heteroxylan polysaccharides is present in plant primary cell walls - Sarah L. Johnston; Roneel Prakash; Nancy J. Chen; Monto H. Kumagai; Helen M. Turano; Janine M. Cooney; Ross G. Atkinson; Robert E. Paull; Roshan Cheetamun; Antony Bacic; David A. Brummell; Roswitha Schröder (Planta, 2013)

Influence of Tyrphostin AG490 on the expression of diabetes-associated markers in human adipocytes - Abdoreza Davoodi-Semiromi; C. H. Wasserfall; A. Hassanzadeh; R. M. Cooper-DeHoff; M. Wabitsch; M. Atkinson (Immunogenetics, 2013)

Systematic review and meta-analysis of epidemiological time-series studies on outdoor air pollution and health in Asia - R. W. Atkinson; A. Cohen; S. Mehta; H. R. Anderson (Air Quality, Atmosphere & Health, 2012)

Species distribution modeling of storm-petrels (Oceanodroma furcata and O. leucorhoa) in the North Pacific and the role of dimethyl sulfide - G. R. W. Humphries; F. Huettmann; G. A. Nevitt; C. Deal; D. Atkinson (Polar Biology, 2012)

Atlantic transport variability at 25° N in six hydrographic sections - C. P. Atkinson; H. L. Bryden; S. A. Cunningham; B. A. King (Ocean Science, 2012)
In January and February 2010, a sixth transatlantic hydrographic section was completed across 25° N, extending the hydrographic record at this latitude to over half a century. In combination with continuous transport measurements made since 2004 at 26.5° N by the Rapid-WATCH project, we reassess transport variability in the 25° N hydrographic record. Past studies of transport variability at this latitude have assumed transport estimates from each hydrographic section to represent annual average conditions. In this study the uncertainty in this assumption is assessed through use of Rapid-WATCH observations to quantify sub-seasonal and seasonal transport variability. Whilst in the upper-ocean no significant interannual or decadal transport variability are identified in the hydrographic record, in the deep ocean transport variability in both depth and potential temperature classes suggests some interannual or decadal variability may have occurred. This is particularly striking in the lower North Atlantic Deep Water where southward transports prior to 1998 were greater than recent transports by several Sverdrups. Whilst a cooling and freshening of Denmark Straits Overflow Water has occurred which is coincident with these transport changes, these water mass changes appear to be density compensated. Transport changes are the result of changing velocity shear in the vicinity of the Deep Western Boundary Current.

Plant growth rates and seed size: a re‐evaluation - Lindsay A. Turnbull; Christopher D. Philipson; Drew W. Purves; Rebecca L. Atkinson; Jennifer Cunniff; Anne Goodenough; Yann Hautier; Jennie Houghton; Toby R. Marthews; Colin P. Osborne; Cloé Paul-Victor; Karen E. Rose; et al. (Ecology, 2012)
Small‐seeded plant species are often reported to have high relative growth rate or RGR. However, because RGR declines as plants grow larger, small‐seeded species could achieve higher RGR simply by virtue of their small size. In contrast, size‐standardized growth rate or SGR factors out these size effects. Differences in SGR can thus only be due to differences in morphology, allocation, or physiology. We used nonlinear regression to calculate SGR for comparison with RGR for 10 groups of species spanning a wide range of life forms. We found that RGR was negatively correlated with seed mass in nearly all groups, but the relationship between SGR and seed mass was highly variable. We conclude that small‐seeded species only sometimes possess additional adaptations for rapid growth over and above their general size advantage.

Integrated catchment management—interweaving social process and science knowledge - A Fenemor; C Phillips; W Allen; RG Young; G Harmsworth; B Bowden; L Basher; PA Gillespie; M Kilvington; R Davies‐Colley; J Dymond; A Cole; et al. (New Zealand Journal of Marine and Freshwater Research, 2011)
This paper provides an overview of the Motueka integrated catchment management (ICM) research programme. This research was based on the thesis that achieving ecosystem resilience at a catchment scale requires active measures to develop community resilience. We define a generic adaptive planning and action process, with associated knowledge management and stakeholder involvement processes, and illustrate those processes with observations from five research themes: (1) water allocation; (2) land use effects on water; (3) land and freshwater impacts on the coast; (4) integrative tools and processes for managing cumulative effects; and (5) building human capital and facilitating community action. Our research clearly illustrates the benefits for effective decision‐making of carrying out catchment scale science and management within collaborative processes which patiently develop trusting relationships. We conclude that coastal catchments should be managed as a holistic continuum from ridge tops to the sea and that some processes like floods or loss of community resilience have decadal consequences, which support the need for long‐term monitoring and investment.

Creative platforms for social learning in ICM: the Watershed Talk project - M Kilvington; M Atkinson; A Fenemor (New Zealand Journal of Marine and Freshwater Research, 2011)
Watershed Talk was an action research project within the Motueka‐based integrated catchment management research programme. It explored processes of dialogue between catchment residents, scientists and resource managers, and examined how design of creative processes can shift people's understanding and develop their capacity to address the complex environmental issues that they face. The project was highly reflective, and examined the potential transformative power of constructive conversation and the means by which social learning platforms can affect the legacy of skills, knowledge and enthusiasm for action amongst participants. Three important elements for the design of platforms for social learning were identified: (1) the value of using principles to guide process design; (2) the potential outcomes from using creative approaches to generate dialogue; and (3) the importance of integrating evaluation and reflection into platform design to both manage the platform and to help cement new learning amongst participants. This paper outlines the fundamental aspects of the Watershed Talk platform design, its implementation, and conclusions drawn from evaluation of the experience.

DNA sequence requirements for hobo transposable element transposition in Drosophila melanogaster - Yu Jung Kim; Robert H. Hice; David A. O’Brochta; Peter W. Atkinson (Genetica, 2011)

Seabed foraging by Antarctic krill: Implications for stock assessment, bentho‐pelagic coupling, and the vertical transfer of iron - Katrin Schmidt; Angus Atkinson; Sebastian Steigenberger; Sophie Fielding; Margaret C. M. Lindsay; David W. Pond; Geraint A. Tarling; Thor A. Klevjer; Claire S. Allen; Stephen Nicol; Eric P. Achterberg (Limnology and Oceanography, 2011)
A compilation of more than 30 studies shows that adult Antarctic krill ( Euphausia superba ) may frequent benthic habitats year‐round, in shelf as well as oceanic waters and throughout their circumpolar range. Net and acoustic data from the Scotia Sea show that in summer 2‐20% of the population reside at depths between 200 and 2000 m, and that large aggregations can form above the seabed. Local differences in the vertical distribution of krill indicate that reduced feeding success in surface waters, either due to predator encounter or food shortage, might initiate such deep migrations and results in benthic feeding. Fatty acid and microscopic analyses of stomach content confirm two different foraging habitats for Antarctic krill: the upper ocean, where fresh phytoplankton is the main food source, and deeper water or the seabed, where detritus and copepods are consumed. Krill caught in upper waters retain signals of benthic feeding, suggesting frequent and dynamic exchange between surface and seabed. Krill contained up to 260 nmol iron per stomach when returning from seabed feeding. About 5% of this iron is labile, i.e., potentially available to phytoplankton. Due to their large biomass, frequent benthic feeding, and acidic digestion of particulate iron, krill might facilitate an input of new iron to Southern Ocean surface waters. Deep migrations and foraging at the seabed are significant parts of krill ecology, and the vertical fluxes involved in this behavior are important for the coupling of benthic and pelagic food webs and their elemental repositories.

Multi-scale GEOBIA with very high spatial resolution digital aerial imagery: scale, texture and image objects - Minho Kim; Timothy A. Warner; Marguerite Madden; Douglas S. Atkinson (International Journal of Remote Sensing, 2011)

Changes in demersal fish assemblages on the west coast of South Africa, 1986–2009 - LJ Atkinson; RW Leslie; JG Field; A Jarre (African Journal of Marine Science, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

The pancreas in human type 1 diabetes - Patrick A. Rowe; Martha L. Campbell-Thompson; Desmond A. Schatz; Mark A. Atkinson (Seminars in Immunopathology, 2011)

Potential mechanisms for achieving agricultural benefits from biochar application to temperate soils: a review - Christopher J. Atkinson; Jean D. Fitzgerald; Neil A. Hipps (Plant and Soil, 2010)

Cadmium, Copper, Iron, and Zinc Concentrations in Kidneys of Grey Wolves, Canis lupus, from Alaska, Idaho, Montana (USA) and the Northwest Territories (Canada) - S. R. Hoffmann; S. A. Blunck; K. N. Petersen; E. M. Jones; J. C. Koval; R. Misek; J. A. Frick; H. D. Cluff; C. A. Sime; M. McNay; K. B. Beckman; M. W. Atkinson; et al. (Bulletin of Environmental Contamination and Toxicology, 2010)

Correlation of major depressive disorder symptoms with FKBP5 but not FKBP4 expression in human immunodeficiency virus–infected individuals - Erick T Tatro; Timothy B Nguyen; Chad A Bousman; Eliezer Masliah; Igor Grant; J Hampton Atkinson; Ian P Everall (Journal of NeuroVirology, 2010)

Utilizing image texture to detect land-cover change in Mediterranean coastal wetlands - S. Berberoğlu; A. Akin; P. M. Atkinson; P. J. Curran (International Journal of Remote Sensing, 2010)

The influence of defined ante-mortem stressors on the early post-mortem biochemical processes in the abdominal muscle of the Norway lobster, Nephrops norvegicus (Linnaeus, 1758) - Sebastian G. Gornik; Amaya Albalat; Robert J. A. Atkinson; Graham H. Coombs; Douglas M. Neil (Marine Biology Research, 2010)

Geostatistically estimated image noise is a function of variance in the underlying signal - A. Asmat; P. M. Atkinson; G. M. Foody (International Journal of Remote Sensing, 2010)

Coral disease following massive bleaching in 2005 causes 60% decline in coral cover on reefs in the US Virgin Islands - J. Miller; E. Muller; C. Rogers; R. Waara; A. Atkinson; K. R. T. Whelan; M. Patterson; B. Witcher (Coral Reefs, 2009)

The costs and benefits of fast living - Karen E. Rose; Rebecca L. Atkinson; Lindsay A. Turnbull; Mark Rees (Ecology Letters, 2009)
Ecology Letters (2009) 12: 1379–1384 Abstract Growth rates play a fundamental role in many areas of biology (Q. Rev. Biol., 67, 1992, 283; Life History Invariants. Some Explorations of Symmetry in Evolutionary Biology, 1993; Philos. Trans. R. Soc. Lond. B Biol. Sci., 351, 1996, 1341; Plant Strategies, Vegetation Processes, and Ecosystem Properties, 2002; Trends Ecol. Evol., 18, 2003, 471; Q. Rev. Biol., 78, 2003, 23; J. Ecol., 95, 2007, 926.) but the cost and benefits of different growth rates are notoriously difficult to quantify (Q. Rev. Biol., 72, 1997, 149; Funct. Ecol., 17, 2003, 328). This is because (1) growth rate typically declines with size and yet the most widely used growth measure – relative growth rate or RGR (conventionally measured as the log of the ratio of successive sizes divided by the time interval) – is not size‐corrected and so confounds growth and size, (2) organisms have access to different amounts of resource and (3) it is essential to allow for the long‐term benefits of larger size. Here we experimentally demonstrate delayed costs and benefits of rapid growth in seven plant species using a novel method to calculate size‐corrected RGR. In control treatments, fast‐growing plants benefited from increased reproduction the following year; however, fast‐growing plants subjected to an experimental stress treatment (defoliation) showed strongly reduced survival and reproduction the following year. Importantly, when growth was estimated using the classical RGR measure, no costs or benefits were found. These results support the idea that life‐history trade‐offs have a dominant role in life‐history and ecological theory and that the widespread failure to detect them is partly due to methodological shortcomings.

Effect of capture method on the physiology and nucleotide breakdown products in the Norway lobster ( Nephrops norvegicus ) - Amaya Albalat; Sebastian G. Gornik; Robert J. A. Atkinson; Graham H. Coombs; Douglas M. Neil (Marine Biology Research, 2009)

Using temperature‐dependent changes in leaf scaling relationships to quantitatively account for thermal acclimation of respiration in a coupled global climate–vegetation model - OWEN K. ATKIN; LINDSEY J. ATKINSON; ROSIE A. FISHER; CATHERINE D. CAMPBELL; JOANA ZARAGOZA‐CASTELLS; JON W. PITCHFORD; F. IAN WOODWARD; VAUGHAN HURRY (Global Change Biology, 2008)
The response of plant respiration ( R ) to temperature is an important component of the biosphere's response to climate change. At present, most global models assume that R increases exponentially with temperature and does not thermally acclimate. Although we now know that acclimation does occur, quantitative incorporation of acclimation into models has been lacking. Using a dataset for 19 species grown at four temperatures (7, 14, 21, and 28 °C), we have assessed whether sustained differences in growth temperature systematically alter the slope and/or intercepts of the generalized log–log plots of leaf R vs. leaf mass per unit leaf area (LMA) and vs. leaf nitrogen (N) concentration. The extent to which variations in growth temperature account for the scatter observed in log–log R –LMA–N scaling relationships was also assessed. We show that thermal history accounts for up to 20% of the scatter in scaling relationships used to predict R , with the impact of thermal history on R –LMA–N generalized scaling relationships being highly predictable. This finding enabled us to quantitatively incorporate acclimation of R into a coupled global climate–vegetation model. We show that accounting for acclimation of R has negligible impact on predicted annual rates of global R , net primary productivity (NPP) or future atmospheric CO 2 concentrations. However, our analysis suggests that accounting for acclimation is important when considering carbon fluxes among thermally contrasting biomes (e.g. accounting for acclimation decreases predicted rates of R by up to 20% in high‐temperature biomes). We conclude that acclimation of R needs to be accounted for when predicting potential responses of terrestrial carbon exchange to climatic change at a regional level.

Neurobehavioral effects of human immunodeficiency virus infection among former plasma donors in rural China - Robert K Heaton; Lucette A Cysique; Hua Jin; Chuan Shi; Xin Yu; Scott Letendre; Donald R Franklin; Christopher Ake; Ofilio Vigil; J Hampton Atkinson; Thomas D Marcotte; Igor Grant; et al. (Journal of NeuroVirology, 2008)

Evidence for widespread cryptic sexual generations in apparently purely asexual Andricus gallwasps - GRAHAM N. STONE; RACHEL J. ATKINSON; ANTONIS ROKAS; JOSÉ‐LUIS NIEVES ALDREY; GEORGE MELIKA; ZOLTAN Ács; GYÖRGY CSÓKA; ALEXANDER HAYWARD; RICHARD BAILEY; CAROLINE BUCKEE; GILEAN A. T. McVEAN (Molecular Ecology, 2008)
Oak gallwasps (Hymenoptera, Cynipidae, Cynipini) are one of seven major animal taxa that commonly reproduce by cyclical parthenogenesis (CP). A major question in research on CP taxa is the frequency with which lineages lose their sexual generations, and diversify as purely asexual radiations. Most oak gallwasp species are only known from an asexual generation, and secondary loss of sex has been conclusively demonstrated in several species, particularly members of the holarctic genus Andricus. This raises the possibility of widespread secondary loss of sex in the Cynipini, and of diversification within purely parthenogenetic lineages. We use two approaches based on analyses of allele frequency data to test for cryptic sexual generations in eight apparently asexual European species distributed through a major western palaearctic lineage of the gallwasp genus Andricus . All species showing adequate levels of polymorphism (7/8) showed signatures of sex compatible with cyclical parthenogenesis. We also use DNA sequence data to test the hypothesis that ignorance of these sexual generations (despite extensive study on this group) results from failure to discriminate among known but morphologically indistinguishable sexual generations. This hypothesis is supported: 35 sequences attributed by leading cynipid taxonomists to a single sexual adult morphospecies, Andricus burgundus, were found to represent the sexual generations of at least six Andricus species. We confirm cryptic sexual generations in a total of 11 Andricus species, suggesting that secondary loss of sex is rare in Andricus .

Unusual new Chaetosphaeria species from New Zealand: Intrafamilial diversity and elucidations of the Chaetosphaeriaceae ‐Lasiosphaeriaceae relationship (Sordariomycetes, Ascomycotina) - Toni J. Atkinson; Andrew N. Miller; Sabine M. Huhndorf; David A. Orlovich (New Zealand Journal of Botany, 2007)
Chaetosphaeria albida, C. bombycina , and C. metallicans are described and compared with other Chaetosphaeria taxa using morphological and molecular methods. The fresh ascomata of C. albida are almost white, translucent, and aereolate; they are papillate with a distinctive 4‐layered peridium, and the ascospores are scolecosporous, multiseptate, and hyaline. C. bombycina is similar, but the fresh ascomata are light fawn‐grey with a reflective silken appearance, non‐papillate, and the similar peridium is 3‐layered. C. metallicans has ascomata which are blue‐black, shiny and metallic when fresh; the thick peridium is heavily melanised, and the ascospores are straight to allantoid, 3‐septate, and hyaline. The scolecosporous ascospores of C. albida and C. bombycina would have traditionally referred these taxa to Lasiosphaeria . However, like C. metallicans , they lack a peridial tomentum, and have asci with light‐refractive, non‐amyloid apical rings, without a sub‐apical globule. Despite the major differences in spore shape and ascomal wall structure, analyses of the LSU and ITS regions of ribosomal DNA suggest that genetically all three fall within Chaetosphaeria , near to C. raciborskii , and in a sister clade to the type species C. innumera . The placement of these species considerably expands current morphological conceptions of Chaetosphaeria , particularly in terms of ascomal wall appearance and structure, and confirms the existence of a scolecosporous group within the genus. in the search for morphological characters which mimic genetic relationships, this study further elucidates the relationship between the Chaetosphaeriaceae and the Lasiosphaeriaceae.

Neurocognitive Effects of Methamphetamine: A Critical Review and Meta-analysis - J. Cobb Scott; Steven Paul Woods; Georg E. Matt; Rachel A. Meyer; Robert K. Heaton; J. Hampton Atkinson; Igor Grant (Neuropsychology Review, 2007)

Occurrence and Distribution of Polycyclic Aromatic Hydrocarbons (PAHs) in Bolgoda and Beira Lakes, Sri Lanka - K. A. S. Pathiratne; O. C. P. De Silva; David Hehemann; Ian Atkinson; Robert Wei (Bulletin of Environmental Contamination and Toxicology, 2007)

A Translational Bioengineering Course Provides Substantial Gains in Civic Scientific Literacy - Rebecca Richards-Kortum; Deanna Buckley; Richard A. Schwarz; E. Neely Atkinson; Michele Follen (Annals of Biomedical Engineering, 2007)

Microhomologies between T-DNA ends and target sites often occur in inverted orientation and may be responsible for the high frequency of T-DNA-associated inversions - Andreas E. Müller; Ross G. Atkinson; Robert B. Sandoval; Richard A. Jorgensen (Plant Cell Reports, 2007)

Idiopathic muscle necrosis in the Norway lobster, Nephrops norvegicus (L.): aetiology, pathology and progression to bacteraemia - I D Ridgway; G D Stentiford; A C Taylor; R J A Atkinson; T H Birkbeck; D M Neil (Journal of Fish Diseases, 2007)
The pathology and progression of idiopathic muscle necrosis (IMN) in Nephrops norvegicus and possible aetiologies have been investigated. Trawl capture, aerial exposure and handling initiate IMN, and the condition can be induced through periods of aerial exposure alone, in the absence of trawling. Within 24–48 h after trawl capture IMN progresses to a multi‐species bacterial septicaemia, with moribund animals exhibiting clinical signs. The aetiology of this condition has been examined using molecular (16S rRNA gene sequencing) and biochemical (standard taxonomic assays, Biolog TM ) criteria to characterize bacterial isolates from moribund and healthy animals. Histopathology of the IMN phase reveals a loss of sarcomeric structure with necrotic lesions containing pyknotic nuclei, fragments of myofibrils and connective tissue elements. In the bacterial phase there is extensive loss of abdominal muscle structure, and the presence of rod‐shaped Gram‐negative bacteria in the degrading tissues. The results demonstrate that the IMN condition is connected to stressful conditions imposed on N. norvegicus , but involves no pathogenic agents. This is followed by an opportunistic bacterial infection that causes further tissue spoilage. It is believed that the primary cause of both IMN and bacteraemia is imposed stress, but they are expressed in different time courses.

Near Real-Time Monitoring and Mapping of Specific Conductivity Levels Across Lake Texoma, USA - Samuel F. Atkinson; Jeff A. Mabe (Environmental Monitoring and Assessment, 2006)

Have the Harmful Effects of Introduced Rats on Islands been Exaggerated? - David R. Towns; Ian A. E. Atkinson; Charles H. Daugherty (Biological Invasions, 2006)

Medium-term impacts of hydraulic clam dredgers on a macrobenthic community of the Adriatic Sea (Italy) - Elisabetta B. Morello; Carlo Froglia; R. James A. Atkinson; P. Geoffrey Moore (Marine Biology, 2006)

hAT element population genetics in Anopheles gambiae s.l. in Mozambique - David A. O’Brochta; Ramanand A. Subramanian; Jamison Orsetti; Edward Peckham; Nicole Nolan; Peter Arensburger; Peter W. Atkinson; Derek J. Charlwood (Genetica, 2006)

Glioma: What is the role of c-Myc, hsp90 and telomerase? - A. Shervington; N. Cruickshanks; H. Wright; R. Atkinson-Dell; R. Lea; G. Roberts; L. Shervington (Molecular and Cellular Biochemistry, 2006)

Pre-maturity α-amylase and incipient sprouting in UK winter wheat, with special reference to the variety Rialto - A. F. Tjin Wong Joe; R. W. Summers; G. D. Lunn; M. D. Atkinson; P. S. Kettlewell (Euphytica, 2005)

Prevalence and differential host‐specificity of two avian blood parasite genera in the Australo‐Papuan region - JON S. BEADELL; EBEN GERING; JEREMY AUSTIN; JOHN P. DUMBACHER; MIKE A. PEIRCE; THANE K. PRATT; CARTER T. ATKINSON; ROBERT C. FLEISCHER (Molecular Ecology, 2004)
The degree to which widespread avian blood parasites in the genera Plasmodium and Haemoproteus pose a threat to novel hosts depends in part on the degree to which they are constrained to a particular host or host family. We examined the host distribution and host‐specificity of these parasites in birds from two relatively understudied and isolated locations: Australia and Papua New Guinea. Using polymerase chain reaction (PCR), we detected infection in 69 of 105 species, representing 44% of individuals surveyed ( n = 428). Across host families, prevalence of Haemoproteus ranged from 13% (Acanthizidae) to 56% (Petroicidae) while prevalence of Plasmodium ranged from 3% (Petroicidae) to 47% (Ptilonorhynchidae). We recovered 78 unique mitochondrial lineages from 155 sequences. Related lineages of Haemoproteus were more likely to derive from the same host family than predicted by chance at shallow (average LogDet genetic distance = 0, n = 12, P = 0.001) and greater depths (average distance = 0.014, n = 11, P Haemoproteus subclades identified in a maximum likelihood phylogeny, host‐specificity was evident up to parasite genetic distances of 0.029 and 0.007 based on logistic regression. We found no significant host relationship among lineages of Plasmodium by any method of analysis. These results support previous evidence of strong host‐family specificity in Haemoproteus and suggest that lineages of Plasmodium are more likely to form evolutionarily–stable associations with novel hosts.

Mass‐transfer limitation of nutrient uptake by a wave‐dominated reef flat community - James L. Falter; Marlin J. Atkinson; Mark A. Merrifield (Limnology and Oceanography, 2004)
Maximum rates of phosphate, nitrate, and ammonium uptake by a reef flat community were estimated from rates of frictional dissipation that were calculated from the attenuation of waves propagating over the Kaneohe Bay Barrier Reef flat. Time‐averaged flow speeds across the entire study area ranged from 0.08 to 0.22 m s −1 . Observed decreases in wave energy fluxes and near‐bottom orbital velocities gave a mean estimate for the bottom friction coefficient ( c f ) of 0.22 ± 0.03. Friction coefficients were used to estimate nutrient mass‐transfer coefficients of 5–9 m d −1 for phosphate and 9–16 m d −1 for ammonium and nitrate. Wave heights offshore of Kaneohe Bay were also used to estimate an annual phosphate mass‐transfer coefficient of 8 ± 2 m d21. This value is similar to a published value of 9 ± 2 m d −1 that was determined from measured changes in phosphate concentrations across the reef flat. We conclude that rates of phosphate uptake by the Kaneohe Bay Barrier Reef flat community are occurring near the limits of mass transfer.

Nutrient uptake by coral-reef microatolls - A. D. L. Steven; M. J. Atkinson (Coral Reefs, 2003)

Thermal acclimation of leaf and root respiration: an investigation comparing inherently fast‐ and slow‐growing plant species - B. R. LOVEYS; L. J. ATKINSON; D. J. SHERLOCK; R. L. ROBERTS; A. H. FITTER; O. K. ATKIN (Global Change Biology, 2003)
We investigated the extent to which leaf and root respiration ( R ) differ in their response to short‐ and long‐term changes in temperature in several contrasting plant species (herbs, grasses, shrubs and trees) that differ in inherent relative growth rate (RGR, increase in mass per unit starting mass and time). Two experiments were conducted using hydroponically grown plants. In the long‐term (LT) acclimation experiment, 16 species were grown at constant 18, 23 and 28 °C. In the short‐term (ST) acclimation experiment, 9 of those species were grown at 25/20 °C (day/night) and then shifted to a 15/10 °C for 7 days. Short‐term Q 10 values (proportional change in R per 10 °C) and the degree of acclimation to longer‐term changes in temperature were compared. The effect of growth temperature on root and leaf soluble sugar and nitrogen concentrations was examined. Light‐saturated photosynthesis (A sat ) was also measured in the LT acclimation experiment. Our results show that Q 10 values and the degree of acclimation are highly variable amongst species and that roots exhibit lower Q 10 values than leaves over the 15–25 °C measurement temperature range. Differences in RGR or concentrations of soluble sugars/nitrogen could not account for the inter‐specific differences in the Q 10 or degree of acclimation. There were no systematic differences in the ability of roots and leaves to acclimate when plants developed under contrasting temperatures (LT acclimation). However, acclimation was greater in both leaves and roots that developed at the growth temperature (LT acclimation) than in pre‐existing leaves and roots shifted from one temperature to another (ST acclimation). The balance between leaf R and A sat was maintained in plants grown at different temperatures, regardless of their inherent relative growth rate. We conclude that there is tight coupling between the respiratory acclimation and the temperature under which leaves and roots developed and that acclimation plays an important role in determining the relationship between respiration and photosynthesis.

Patterns of Hermes transposition in Drosophila melanogaster - N. Guimond; D. K. Bideshi; A. C. Pinkerton; P. W. Atkinson; D. A. O'Brochta (Molecular Genetics and Genomics, 2003)

Response of freshwater microcosm communities to nutrients, fish, and elevated temperature during winter and summer - D. McKee; D. Atkinson; S. E. Collings; J. W. Eaton; A. B. Gill; I. Harvey; K. Hatton; T. Heyes; D. Wilson; B. Moss (Limnology and Oceanography, 2003)
Under conditions of stress, shallow freshwater ecosystems can undergo a state change characterized by the rapid loss of macrophytes and subsequent dominance of phytoplankton. Elevated water temperature may promote such change. Here we report the impact of two warming regimes (continuous 3°C above ambient and 3°C above ambient during summer only), with two nutrient loadings and the presence or absence of fish, on 48 microcosm ecosystems created to mimic shallow pond environments. We found that warming did not significantly encourage phytoplankton blooms, even in combination with increased nutrients and fish. Instead, macrophyte communities remained dominant. Macrophyte‐associated invertebrates (gastropods and ostracods) increased in numbers in the warmed microcosms, potentially helping to stabilize the macrophyte communities. Nevertheless, warming produced trends in water chemistry that could be problematic. It increased phosphorus concentrations, total alkalinity, and conductivity. It decreased pH and oxygen saturation and increased the frequency of severe deoxygenation. These trends were largely independent of the other experimental treatments and support the suggestion that moderate warming has the potential to exacerbate existing eutrophication problems.

Trimethyltin-induced neurogenesis in the murine hippocampus - G. Jean Harry; Christopher A. McPherson; Robert N. Wine; Kelly Atkinson; Christian Lefebvre d'Hellencourt (Neurotoxicity Research, 2003)

Seasonal differences in citrate synthase and digestive enzyme activity in larval and postlarval antarctic krill, Euphausia superba - B. Meyer; R. Saborowski; A. Atkinson; F. Buchholz; U. Bathmann (Marine Biology, 2002)

The incidence and diversity of Wolbachia in gallwasps (Hymenoptera; Cynipidae) on oak - A. Rokas; R. J. Atkinson; J.‐L. Nieves‐Aldrey; S. A. West; G. N. Stone (Molecular Ecology, 2002)
Wolbachia bacteria infect ≈ 20% of all insect species, and cause a range of alterations to host reproduction, including imposition of thelytoky. The incidence and phenotypic impact of Wolbachia remains to be established in many insect taxa, and considerable research effort is currently focused on its association with particular reproductive modes and the relative importance of the various pathways via which infection occurs. Gallwasps represent an attractive system for addressing these issues for two reasons. First, they show a diversity of reproductive modes (including arrhenotoky, thelytoky and cyclical parthenogenesis) in which the impact of Wolbachia infection can be examined. Second, they occupy two intimately linked trophic niches (gall‐inducers and inquilines) between which there is potential for the horizontal exchange of Wolbachia infection. In the arrhenotokous gallwasp lineages screened to date (the herb‐galling ‘Aylacini’ and the rose‐galling Diplolepidini), Wolbachia infection always induces thelytoky. The impact of Wolbachia in other arrhenotokous clades, and in the cyclically parthenogenetic clades remains unknown. Here we use polymerase chain reaction (PCR) screening and sequence data for two Wolbachia genes ( wsp and ftsZ ) to examine the prevalence and incidence of Wolbachia infection in 64 species (a total of 609 individuals) in two further tribes: the arrhenotokous inquilines (tribe Synergini), and the cyclically parthenogenetic oak gallwasps (tribe Cynipini). We ask: (i) whether Wolbachia infection has any apparent impact on host reproduction in the two tribes and (ii) whether there is any correlation between Wolbachia infection and the apparent lack of an arrhenotokous generation in many oak gallwasp life cycles. We show: (i) that Wolbachia infection is rare in the Cynipini. Infected species show no deviation from cyclical parthenogenesis, and infection is no more common in species known only from a thelytokous generation; (ii) that there is a higher incidence of infection within the arrhenotokous inquilines, and generally in gallwasp tribes without cyclical parthenogensis; (iii) all Wolbachia ‐positive inquiline species are known to possess males, implying either that Wolbachia infection does not result in loss of sex in this tribe or, more probably, that (as for some rose gallwasps) Wolbachia infection leads to loss of sex in specific populations; and (iv) although we find some inquilines and gall inducers to be infected with Wolbachia having the same wsp sequence, these hosts are not members of the same gall communities, arguing against frequent horizontal transmission between these two trophic groups. We suggest that exchange may be mediated by the generalist parasitoids common in oak galls.

Feeding and energy budgets of Antarctic krill Euphausia superba at the onset of winter—I. Furcilia III larvae - B. Meyer; A. Atkinson; D. Stöbing; B. Oettl; W. Hagen; U. V. Bathmann (Limnology and Oceanography, 2002)
Physiological condition and feeding behavior of furcilia larvae were investigated in autumn (April 1999) in the southwestern Lazarev Sea prior to the critical overwintering period. Furcilia stage III (FIII) larvae were most abundant, so only these were used for all analyses (dry mass [DM], elemental and biochemical composition, gut content) and experiments (metabolic and ingestion rates, selective feeding behavior). Chlorophyll a (Chl a) concentrations in the mixed layer were ≪0.1 µg L -1 . Respiration rates of freshly caught FIII larvae were between 0.4 and 1.2 µl O 2 mg -1 DM h -1 , similar to larvae fed for 7 d on high food concentrations (4 µg Chl a L -1 ). Excretion rates ranged between 0.01 and 0.02 µg NH 4 mg -1 DM h -1 . Their atomic O:N ratio of 72 indicated that lipids were the main metabolic substrate of FIII larvae in the field. The daily C ration ranged from 0.4% at the lowest food concentration of 3 µg C L -1 to 28% at the highest enriched food concentration of 216 µg C L -1 , whereas clearance rates decreased with increasing food concentrations. In natural seawater, 115 ml mg -1 C h -1 , and in natural seawater enriched with ice biota, 24 ml mg -1 C h -1 , the clearance rates on specific phytoplankton taxa revealed no significant difference across a food size range of 12–220 µm. The study suggests that during periods of low food supply in the water column, larvae have to exploit ice biota to cover their metabolic demands.

Feeding and energy budgets of Antarctic krill Euphausia superba at the onset of winter—II. Juveniles and adults - A. Atkinson; B. Meyer; D. Stuϋbing; W. Hagen; K. Schmidt; U. V. Bathmann (Limnology and Oceanography, 2002)
The overwintering success of Euphausia superba is a key factor that dictates population size, but there is uncertainty over how they cope with the scarcity of pelagic food. Both nonfeeding strategies (reduced metabolism, lipid use, or shrinkage in size) and switching to other foods (carnivory, ice algae, or detritus) have been suggested. We examined these alternatives in the southwest Lazarev Sea in autumn (April 1999), when sea ice was forming and phytoplankton was at winter concentrations. Both juveniles and adults had a very high lipid content (36% and 44% of dry mass, respectively) of which >40% was phospholipid. However, their low O:N ratios suggested that these reserves were not being used. Results from gut contents analysis and large volume incubations agreed that juveniles fed mainly on phytoplankton and adults fed on small (

Directing Research to Reduce the Impacts of Nonindigenous Species - James E. Byers; Sarah Reichard; John M. Randall; Ingrid M. Parker; Carey S. Smith; W. M. Lonsdale; I. A. E. Atkinson; T. R. Seastedt; Mark Williamson; E. Chornesky; D. Hayes (Conservation Biology, 2002)
Management of nonindigenous species is a crucial aspect of maintaining native biodiversity and normal ecosystem functions. We attempt to guide researchers in developing projects that will be of use to conservation practitioners, tangibly improving applied conservation measures. We advocate a directed approach for conservation research to aid in prioritizing nonindigenous species for intervention by resource managers. This approach includes outlining what needs to be known to make such relative judgments about the impacts of nonindigenous species and the most promising methods by which to obtain such information. We also address active measures that should be taken once priorities have been set, highlighting the roles of risk assessment and research in improving control efforts. Ultimately, a better match between research and practical conservation needs should result in more effective reduction of the effects of nonindigenous species on native species.

Sucrose Phosphate Synthase Genes in Plants Belong to Three Different Families - Georg Langenkämper; Raymond W.M. Fung; Richard D. Newcomb; Ross G. Atkinson; Richard C. Gardner; Elspeth A. MacRae (Journal of Molecular Evolution, 2002)

Effects of a hydroxy-cinnamoyl conjugate of spermidine on arthropod neuromuscular junctions - Klose M.; Atkinson J.; Mercier A. (Journal of Comparative Physiology A, 2002)

Ammonium regeneration by Antarctic mesozooplankton: an allometric approach - Atkinson A.; Whitehouse M. (Marine Biology, 2001)

Uptake of estrone from the water column by a coral community - Tarrant A.; Atkinson M.; Atkinson S. (Marine Biology, 2001)

A microbiological survey of Montserrat Island hydrothermal biotopes - Tony Atkinson; Steven Cairns; D. A. Cowan; Michael J. Danson; David W. Hough; D. Barrie Johnson; Paul R. Norris; Neil Raven; Clare Robinson; Rob Robson; Richard J. Sharp (Extremophiles, 2000)

MDH1: an apple homeobox gene belonging to the BEL1 family - Yi-Hu Dong; Jia-Long Yao; Ross G. Atkinson; Joanna J. Putterill; Bret A. Morris; Richard C. Gardner (Plant Molecular Biology, 2000)

Zonal distribution and seasonal vertical migration of copepod assemblages in the Scotia Sea - A. Atkinson; J. D. Sinclair (Polar Biology, 2000)

Polygalacturonase gene expression in kiwifruit: relationship to fruit softening and ethylene production - Zhong-Yan Wang; Elspeth A. MacRae; Michele A. Wright; Karen M. Bolitho; Gavin S. Ross; Ross G. Atkinson (Plant Molecular Biology, 2000)

Identification of a novel four-domain member of the proteinase inhibitor II family from the stigmas of Nicotiana alata - Elizabeth A. Miller; Marcus C.S. Lee; Angela H.O. Atkinson; Marilyn A. Anderson (Plant Molecular Biology, 2000)

Atmospheric Response To Spatial Variations In Concentration And Size Of Polynyas In The Southern Ocean Sea-Ice Zone - R. A. Dare; B. W. Atkinson (Boundary-Layer Meteorology, 2000)

Transformations of Pesticides in the Atmosphere: A State of the Art - Roger Atkinson; Rob Guicherit; Ronald A. Hites; Wolf-Ulrich Palm; James N. Seiber; Pim de Voogt (Water, Air, & Soil Pollution, 1999)

Obituary - I. A. E. Atkinson (New Zealand Journal of Botany, 1999)

Evaluation of the Best disease gene in patients with age-related macular degeneration and other maculopathies - R. Allikmets; Johanna M. Seddon; Paul S. Bernstein; A. Hutchinson; Andrew Atkinson; Sanjay Sharma; Bernard Gerrard; W. Li; Michael L. Metzker; Claes Wadelius; C. Thomas Caskey; Michael Dean; et al. (Human Genetics, 1999)

Integration specificity of the hobo element of Drosophila melanogaster is dependent on sequences flanking the integration site - Kenneth J. Saville; William D. Warren; Peter W. Atkinson; David A. O'Brochta (Genetica, 1999)

Comparison of gut morphology and gut microflora of seven species of mud shrimp (Crustacea: Decapoda: Thalassinidea) - E. H. Pinn; L. A. Nickell; A. Rogerson; R. J. A. Atkinson (Marine Biology, 1999)

Apple ACC-oxidase and polygalacturonase: ripening-specific gene expression and promoter analysis in transgenic tomato - Ross G. Atkinson; Karen M. Bolitho; Michele A. Wright; Teresa Iturriagagoitia-Bueno; Suzanne J. Reid; Gavin S. Ross (Plant Molecular Biology, 1998)

GUS expression patterns from a tobacco yellow dwarf virus-based episomal vector - P. D. Needham; R. G. Atkinson; B. A. M. Morris; R. C. Gardner; A. P. Gleave (Plant Cell Reports, 1998)

Expression of an engineered cysteine proteinase inhibitor (Oryzacystatin-IΔD86) for nematode resistance in transgenic rice plants - P. Vain; B. Worland; M. C. Clarke; G. Richard; M. Beavis; H. Liu; A. Kohli; M. Leech; J. Snape; P. Christou; H. Atkinson (Theoretical and Applied Genetics, 1998)

Radiometric dating of the Middle Palaeolithic tool industry and associated fauna of Pin Hole Cave, Creswell Crags, England - Roger M. Jacobi; Peter J. Rowe; Mabs A. Gilmour; Rainer Grün; Timothy C. Atkinson (Journal of Quaternary Science, 1998)

Radiometric dating of the Middle Palaeolithic tool industry and associated fauna of Pin Hole Cave, Creswell Crags, England - Roger M. Jacobi; Peter J. Rowe; Mabs A. Gilmour; Rainer Grün; Timothy C. Atkinson (Journal of Quaternary Science, 1998)

Molecular characterisation of a cDNA sequence encoding the backbone of a style-specific 120 kDa glycoprotein which has features of both extensins and arabinogalactan proteins - Carolyn J. Schultz; Karin Hauser; Jan L. Lind; Angela H. Atkinson; Zhao-yan Pu; Marilyn A. Anderson; Adrienne E. Clarke (Plant Molecular Biology, 1997)

Observations on the Burrows and Burrowing Behaviour of: Squilla mantis L. Crustacea: Stomatopoda - R. J. A. ATKINSON; C. FROGLIA; E. ARNERI; B. ANTOLINI (Marine Ecology, 1997)
The burrows of Squilla mantis are described from polyester resin casts taken at two Adriatic sites near Ancona. Typically, burrows had two openings, one of which was larger than the other, and were basically U‐shaped. An interesting association with the little‐known caridean shrimp Athanas amazone was observed. The sediments occupied by S. mantis were silty sands and sandy muds. Field observations of S. mantis and other species on the same grounds are presented and some information on burrow density is given, derived from burrow counts using underwater television. Burrowing behaviour is described from observations of animals transferred to laboratory aquaria.

Biochemical composition of Nephrops norvegicus : changes associated with ovary maturation - I. D. Tuck; A. C. Taylor; R. J. A. Atkinson; M. E. Gramitto; C. Smith (Marine Biology, 1997)

Structure and grazing impact of the mesozooplankton community during late summer 1994 near South Georgia, Antarctica - E. A. Pakhomov; H. M. Verheye; A. Atkinson; R. K. Laubscher; J. Taunton-Clark (Polar Biology, 1997)

In situ hybridization in Actinidia using repeat DNA and genomic probes - G. Yan; R. G. Atkinson; A. R. Ferguson; M. A. McNeilage; B. G. Murray (Theoretical and Applied Genetics, 1997)

TheHermes element fromMusca domestica can transpose in four families of cyclorrhaphan flies - Abhimanyu Sarkar; Craig J. Coates; Steven Whyard; Ute Willhoeft; Peter W. Atkinson; David A. O'Brochta (Genetica, 1997)

The Hermes element from Musca domestica can transpose in four families of cyclorrhaphan flies - Abhimanyu Sarkar; Craig J. Coates; Steven Whyard; Ute Willhoeft; Peter W. Atkinson; David A. O'Brochta (Genetica, 1997)

An improved multi-element measurement of mineral absorption in the piglet utilizing the fecal monitoring technique - Rosalind S. Gibson; Ian L. Gibson; Colin E. Webber; Stephanie A. Atkinson (Biological Trace Element Research, 1988)

Kinetics of the atmospherically important gas-phase reactions of a series of trimethyl phosphorothioates - Mark A. Goodman; Sara M. Aschmann; Roger Atkinson; Arthur M. Winer (Archives of Environmental Contamination and Toxicology, 1988)